GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 174481060 species occurrences available in GBIF matching the query: TaxonKey: Plantae or Xanthium L.. The dataset includes 174481060 records from 2858 constituent datasets: 41 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 3565 records from Bioimages. 24 records from Naturalis Biodiversity Center (NL) - Crustacea. 142 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 1348 records from Inventory of Wari maro forest (Benin). 82 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1093 records from National Biodiversity Data Bank. Observation records, 1900-2014. 3104 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 156127 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 5952 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 2 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 10046 records from Guadeloupe_Herbier. 3 records from Plan de vertebrados de la Patagonia. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 12529 records from JOI - Herbário Joinvillea. 14737 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 1650 records from University of Calgary Herbarium. 3367614 records from OEH Atlas of NSW Wildlife. 2771 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 5771 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 330033 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 8725276 records from Botanical Society of the British Isles - Vascular Plants Database. 22280 records from HUEM - Herbário da Universidade Estadual de Maringá. 67913 records from HUFU - Herbarium Uberlandense. 1018278 records from Phanerogamic Botanical Collections (S). 97808 records from Jordal. 42 records from MVZ Herp Collection (Arctos). 190 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 216 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 62282 records from PRECIS (KwaZulu-Natal Herbarium). 712 records from Herbier G. Garapin (BOUM). 81449 records from University of Vienna, Institute for Botany - Herbarium WU. 4 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 1950 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 16661 records from UFG - Herbário da Universidade Federal de Goiás. 1 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 1702 records from BioGIS - Bryophytes - HUJ collections. 5717 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 653 records from Colección nacional de palmas de Colombia - JBQ. 39 records from Lindesnes. 1201 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 1791 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 147 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 3 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 3282 records from Marine species distributions in Irish coastal waters. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 55665 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 29 records from Coastal and marine species. 10355 records from Census of the flora of Benin. 3036 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 141138 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 21892 records from Tromsø Museum, Bryophytes. 34 records from New records in vascular plants alien to Kyrgyzstan. 40098 records from Online Atlas of vascular plants 2012-2020. 12357 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 857 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 52990 records from IAC - Herbário do Instituto Agronômico de Campinas. 2163 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 104 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 1 records from Fossil (SMNH-FO). 16 records from Palaeobiology collection, FAU Erlangen. 297 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 47215 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 2777 records from Portuguese Seaweeds. 10097 records from Herbarium Vonderau - FULD. 1357 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 35306 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 4358 records from Herbarium WRSL, Flora of the Silesia. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 144922 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 1 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 1 records from CAS Entomology (ENT). 1 records from Red list project inventory, bryophytes. 3 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 4634297 records from Naturalis Biodiversity Center (NL) - Botany. 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 100 records from Brock University Herbarium (BU). 7745 records from PlutoF platform observations. 24947 records from Herbarium Senckenbergianum (GLM) - Lichenes. 48021 records from SPSF - Herbário Dom Bento José Pickel. 30 records from Type Specimen Database of Museum and Institute of Zoology PAS. 23290 records from SANT-Algae. 128231 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 1117757 records from PRECIS. 6 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 1198 records from monocotyledonous_geophytes_of_fergana_valley. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 28 records from SMNS Palaeontological collection - Amber and fossil insects. 12470 records from EPA River Biologists data. 5505 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 150 records from Paläontologie Marburg. 290 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 881 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 163193 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 53865 records from SPF - Herbário da Universidade de São Paulo. 177886 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 66721 records from SANT herbarium vascular plants collection. 2332 records from Collection du Musée d'Histoire Naturelle de Nice. 9349 records from Harriet Irving Botanical Gardens (HIBG). 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 17519 records from Species plots from the Norwegian Vegetation Mapping Programme. 616 records from Collection of botanical drawings by Georg Schweinfurth at B. 268 records from mcme_uplb_museum_plant_collection. 46388 records from UFP - Herbário UFP - Geraldo Mariz. 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 61 records from Registros restauración ecológica- Magdalena medio. 1 records from Merseyside BioBank - North Merseyside Insects (verified). 561 records from NPL collections. 99 records from French national collection of Solanum tuberosum. 57305 records from Colección Herbario Federico Medem Bogotá - FMB. 1447 records from Local BioBlitz Challenge 2013. 18272 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 208 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 4826 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 900520 records from FLORIVON. 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 2 records from Highland Biological Recording Group - HBRG Insects Dataset. 89662 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 385002 records from Species data extracted from the National Vegetation Database. 108 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2213466 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 1329 records from API_CRSN_Data. 7671 records from HERBAM - Herbário da Amazônia Meridional. 23004 records from Herbario Pontificia Universidad Javeriana. 105962 records from ICN - Herbário do Instituto de Ciências Naturais. 13 records from Meiobenthos of target sites of Crimea in 2009/2010. 68304 records from IICT Herbário LISC. 85003 records from Herbario Universidad de Antioquia (HUA). 7 records from Lund Museum of Zoology - Insect collections (MZLU). 88 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 5129 records from URM - Herbário Pe. Camille Torrand. 2433 records from Inventario Español de Especies Terrestres (MAGRAMA). 17 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 79603 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 13 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 44 records from Solanum_baretiae. 7460 records from BioGIS - Vascular plants - Israeli Gene Bank. 2 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 3257 records from fundiv france database. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 4846 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 127 records from Entomology, Natural History Museum, University of Oslo. 3779762 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 254 records from Inventario de Plantas Mámbita. 8589 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 68 records from BTCV Scotland - BTCV wildlife counts recording workshops. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 7527 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 30 records from Hosted Invertebrate Collection 01. 374 records from published_chenopodium_vulvaria_observations. 5 records from IMOS - AusCPR: Phytoplankton Abundance. 119300 records from The digitization of plant specimens of NTU. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 1736164 records from SA Flora (BDBSA). 8880 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 314 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 45989 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 1071 records from NINA Vanndata øvrige arter. 17 records from AM: Freshwater Invertebrates (1900-2005). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 1 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 218069 records from Phytochorologie des départements français. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 4758 records from SMDB - Santa Maria Departamento de Biologia. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 4 records from Dragonfly Ireland. 4231 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 172850 records from BioFokus. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 216335 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 4498 records from Colección Herbario Universidad Católica de Oriente. 326 records from Culture Collection of Cryophilic Algae. 303 records from Clare Biological Records Centre dataset. 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 256 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 1 records from University of Florida Vertebrate Paleontology. 184 records from Bioblitz 2013 Copenhagen Denmark. 127876 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 72227 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 1881 records from Monitoring data from the federal state Bavaria (Germany). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 7469 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 51678 records from CESJ - Herbário Leopoldo Krieger. 50 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 13716 records from OUPR - Herbário "Professor José Badini". 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 718 records from HAS-Algae - Coleção Ficológica do HAS. 868 records from Kartlegging av spredning av fremmede bartrær. 15866 records from HAMAB - Herbário Amapaense. 32 records from CUMV Fish Collection (Arctos). 74658 records from Irish Vascular Plant Data - Paul Green. 6065 records from LISU Herbario Angola. 3866312 records from FlorKart - FlorenKartierung Gefaesspflanzen. 89576 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 1859 records from Banc de Germoplasma Vegetal de les Illes Balears-JBS. 352645 records from Plantae of Costa Rica (INBio). 5967 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 535 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 768440 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 5960641 records from Artdata. 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 13280 records from Herbier du Bénin. 76 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 9027 records from Flora of Słowiński National Park, Poland. 1843 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 2 records from Museum Victoria provider for OZCAM. 157 records from The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forest.. 2884 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 78986 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 292 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 12066 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1802 records from Flora of tanzania. 2966 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 274890 records from MBM - Herbário do Museu Botânico Municipal. 777 records from INRA-Versailles Arabidopsis natural variants. 1 records from Ohio University Invertebrate Paleontology Collection. 368 records from Algae (KBRC-AG). 49 records from The "Martian" flora: new collections of vascular plants, lichens, fungi, algae, and cyanobacteria from the Mars Desert Research Station, Utah. 1 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 235598 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 10895 records from Stabbetorp - Floristiske registreringer 2016. 527 records from Inventaire floristique de Beza Mahafaly. 8590 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 4489 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 997 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 2865 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 1 records from Insecta of Costa Rica (INBio). 258 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 5 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 8804 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 906 records from Digital Florula - Las Cruces Biological Station. 24121 records from Endemic plants of the Congo basin. 2031 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 1 records from SDSM Botany and Paleobotany Collections. 3 records from Chrysomelidae of the Carpathians. 108494 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 137807 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 5409 records from Algae (S). 51 records from Araneae Collection. 19736 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 76623 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 145209 records from OHN. 429 records from TPWD HARC Texas Coastal Fisheries, Corpus Christi Bay Gill Net. 14 records from Lund Museum of Zoology (MZLU). 16 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 659782 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 365952 records from Données ONF Faune-Flore-Fonge. 1513 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 6329 records from FCAB - Herbário Friburguense. 30143 records from Herbier de Nouvelle-Calédonie. 1 records from CAS Invertebrate Zoology (IZ). 987 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 6808 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 1029 records from Freshwater plants of Cameroon. 2 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 24763 records from Tallinn Botanic Garden. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 20 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 2742 records from Plant (KIWE-PL). 127 records from Inventory of Bonou, Kilibo and Lama forests (South and centre Benin). 9 records from Chenopodium vulvaria. 11187 records from Herbarium areqvipense (HUSA). 1640 records from NCSM PaleoBotany Collection. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 8285 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 66 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 856 records from Culture Collection of Algae. 8 records from Invert Paleo Specimens. 388 records from Algae, Norwegian College of Fishery Science. 31 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 1385 records from Plant observations from Białowieża National Park. 17009 records from Norwegian Biodiversity Information Centre - Other datasets. 144 records from Checklist of Fabaceae Lindley in Balaghat Ranges of Maharashtra, India. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 4 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 377 records from Herbario MAIA, colección de Eucaliptus del INIA-CIFOR. 327 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 622 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 1 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 2952 records from Geneva Herbarium – Burnat Herbarium (G-BU). 3283 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 67 records from Museum of Comparative Zoology, Harvard University. 12537 records from Herbarium of the Université Libre de Bruxelles. 8099 records from tef-database. 18 records from Staatliches Naturhistorisches Museum Braunschweig - Coleoptera Collection. 119 records from Naturalis Biodiversity Center (NL) - Cnidaria. 4964784 records from Australia's Virtual Herbarium. 1667138 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 35931 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 431 records from Plantas Bosque Seco Chicamocha. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 38508 records from Herbier de Strasbourg. 1 records from Flora of Suriname, volume VI, part I. 23078 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 814 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 197616 records from Vascular Plant Herbarium, UiB. 30 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 42541 records from Kathryn Kalmbach Herbarium. 2052 records from Banco de Germoplasma del Jardín Botánico Atlántico. 15 records from Chenopodium. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 153532 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 200887 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 496 records from Colección Limnológica Universidad de Antioquia. 21983 records from Natural History Museum Maastricht (NL) - Herbarium. 2 records from Naturalis Biodiversity Center (NL) - Collembola. 3 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 1910783 records from Consortium of California Herbaria. 842 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 169 records from The Pteridaceae family diversity in Togo. 98 records from Colección Nacional de Heliconias. 761 records from Monitoring data from the federal state Hesse (Germany). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 330543 records from iNaturalist Research-grade Observations. 807 records from Reunion_Coffea. 409 records from Herbario MAIA, colección de Quercus del INIA-CIFOR. 806 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 18899 records from UCBG TAPIR Provider. 257947 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 4858 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 3669 records from ARKO strandeng. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 16 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 171056 records from CONN. 29998 records from HUCS - Herbário da Universidade de Caxias do Sul. 17187 records from BioGIS - Vascular plants - HUJ Herbarium. 3753 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 50874 records from H.A. Stephens Herbarium. 3 records from Upper Silesian Museum, Bird Observations. 157 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 319 records from HTSAw - Xiloteca do Trópico Semiárido. 1587 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 1802 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 5 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 6845 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 4498 records from Flora of Japan Specimen Database. 6736 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 9 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 21713 records from University of Lethbridge Herbarium (LEA). 204 records from Invertebrates Collection of the Swedish Museum of Natural History. 3 records from Fungi Collection. 209189 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 8 records from Alien Species in Poland - Animals. 93358 records from Estonian Museum of Natural History. 30 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 979 records from minsok. 4745 records from Collection botanique Le Grand A. (BOUM). 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 1752 records from Herbier National de Mauritanie (HNM). 43366 records from University of California Museum of Paleontology. 7605 records from NINA botanical collection. 1914 records from Macrophytes_CLF. 416668 records from Meadow and Pasture Inventory (SJV). 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 7045 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 1 records from DMNS Marine Invertebrate Collection (Arctos). 84032 records from BioGIS - Vascular plants - INPA database. 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 140 records from KUBI Vertebrate Paleontology Collection. 94636 records from ALCB - Herbário Alexandre Leal Costa. 6100 records from HUSC - Herbário Unisanta. 392910 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 8794 records from HPBR - Herbário Padre Balduino Rambo. 532 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 1489 records from Herbarium Rhoenmuseum Fladungen. 116080 records from Estonian University of Life Sciences. 106 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 40 records from Countryside Council for Wales - Shad Monitoring data. 1 records from CAS Ichthyology (ICH). 16 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 1258111 records from NMNH occurrence DwC-A. 601 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 13447 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 788 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 4 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 8421 records from BioMar - LIFE project. 4963 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 39606 records from BioGIS - Vascular plants - A. Danin's point database. 1353 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 188 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 805 records from Monitoring data from the federal state Saxony (Germany). 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 19449 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 1 records from Birdrace_Schräge_Vögel-Herford. 4 records from Birdrace-Die_Nachtraben-Stuttgart. 22 records from Im Bauerngarten. 122 records from VFD-H: Rheingau: Pferdeweide Loock. 121 records from Klasse 3a. 122 records from Seewasen. 67 records from Siegen/ Gymnasium Am Löhrtor. 23 records from Borkhart. 219 records from Küstenschutzwald. 141 records from FNL e.V.. 3 records from Spechtwald. 198 records from Kremmer Luch. 169 records from Beweidungsprojekt an der Nesse. 112 records from Flora. 34 records from Feriendorf Ober-Seemen. 50805 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 22 records from Förderzentrum Schmölln. 75 records from Kloster Eberbach. 91 records from LauWi. 97 records from Ehmkendorf. 49 records from Grenzturm Hohen Neuendorf. 34 records from Lech 2001. 149 records from Isarufer. 31 records from Fledermaus. 32 records from Waldsee. 28 records from Feriendorf des Kreises Gedern (Ober-Seemen). 87 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 152 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 112 records from Hochschulgelände (Bremen). 74 records from Biotop "Kohlbeke" (Berlin-Marzahn). 35 records from Heidesee / Halle. 40 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 5011 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 29 records from Berlin - Treptower Park / Karpfenteich. 41 records from "Schlechteberg" Ebersbach/Sa.. 41 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 65 records from Fuchsloch (Mohlsdorf/Ostthüringen). 65 records from Naturgrundstück (Eutin). 27 records from Lassentiner Moor (Niepars). 140 records from Kiesgruben Wemb. 9 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 96 records from Truppenübungsplatz Panzerkaserne Böblingen. 60 records from Schulgarten mit Klasse 8a (Essen). 96 records from Döchtbühlwald (Bad Waldsee). 40 records from Roter Berg Werdau (Leubnitz). 43 records from Waldhusener Moor (Lübeck-Kücknitz). 120 records from Föhrenried (Fronreute und Baindt). 15 records from AKG-Bensheim. 144 records from Artenvielfalt Kreis Gießen. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 34 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 162 records from Regenrückhaltebecken (Zeulenroda). 22 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 186 records from Deponie Klausdorf. 12 records from Alter Nördlicher Friedhof (München). 19 records from Motzener Tonsee. 134 records from Stadtpark Herzberg (Elster). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 68 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 74 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 93 records from Zielbach (Töll). 75 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 50 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 216 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 16 records from Südpark (Bochum-Wattenscheid). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 33 records from Flusswerder in der Weser (Hameln). 60 records from Wedeler Au. 129 records from Bodenseeufer Radolfzell. 41 records from Zitadelle Berlin-Spandau (7b). 33 records from Kabelskebach (Kabelsketal, Saalkreis). 77 records from Steinbruch Mainz-Weisenau. 106 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 211 records from Triebesbach (Zeulenroda-Triebes). 43 records from Wiese am Unterbecken. 64 records from Ortelsbruch - Hangmoor bei Morbach. 13 records from Dellwiger Bach (Dortmund). 29 records from verschiedene Kleingewässer um Oldenburg/Holstein. 38 records from "Schwarzes Teich" (Waldpark Radebeul). 79 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 65 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 24 records from Örtzemündung (Stedden). 14 records from Hainbachtal in Oelsnitz/V.. 191 records from Wangerooge. 6 records from Kita-Wäldchen Fuchsturmweg Jena. 128 records from Umgebung der Grundschule Oderberg. 92 records from Naturhausgarten. 41 records from Die Wuhle. 99 records from Steinbruch Mainz-Weisenau, 2. Jahr. 23787 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 72 records from Wirbach. 190 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 96 records from Paul-Gerhardt-Schule Dassel. 145 records from privater Garten. 141 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 111 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 51 records from Alter Kreidebruch Saßnitz/Rügen. 87 records from Schussenaue bei Berg. 263 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 59 records from Rund um das LUGY. 231 records from Ried und Sand - Artenvielfalt durch Beweidung. 24 records from Nationalpark Harz Schul-AG Braunlage. 22 records from Junge Heide, Radebeul/Dresden. 44 records from Insektenvielfalt Ahe/Weichelsee. 57 records from Schulgarten Hans-Carossa-Oberschule. 38 records from Ludwigshofen. 66 records from Landschaftsschutzgebiet Buchhorst 3. 85 records from Stever. 43 records from Bolzplatz. 14 records from Spielwiese. 6 records from Kindergarten. 64 records from Wassermann. 8 records from Willersalpe. 51 records from GymnQuerfurt. 27 records from Erft in Selikum (Neuss). 77 records from Landschaftsschutzgebiet "Holmer Sandberge". 33 records from Varnhalt. 18 records from Mittelstreifen. 66 records from Mainufer. 46 records from Rund ums Ökohaus (Würzburg). 18 records from Schulhof Sandhofenschule (Mannheim). 104 records from Brander Wald (Stolberg). 48 records from Wiesenbiotop am Wasserturm. 54 records from Balkon (Norderstedt). 76 records from Spießwoogtal / Königsbruch (Fischbach). 108 records from Artenvielfalt im Beckerbruch (Dessau). 8 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 36 records from Wasserwerkspark (Chemnitz). 69 records from Düne am Ulvenberg (Darmstadt). 28 records from Sandgrube Zaisertshofen. 91 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 76 records from Ökologischer Weinberg (Guntersblum). 16 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 38 records from Schwanseepark (87645 Schwangau). 78 records from Wirbach-Taubental (Bad Blankenburg). 35 records from Trockenrasen bei Dörndorf. 16 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 70 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 1030 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 35 records from Urwald 3 (Bad Waldsee). 52 records from Trockenrasen Franzigmark (Halle/Saale). 39 records from Streuobstwiesengelände St.Meinrad Gymnasium. 25 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 33 records from Wiese und Bach beim Unterbecken (Markersbach). 39 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 236 records from Garten J. Scherrer (Lachen-Speyerdorf). 44 records from Mauernacker (Wettsaasen). 5 records from Streuobstwiese (Mittelgasse 4). 9 records from Schutzgebiet Ochtersum. 35 records from Tag der Artenvielfalt BUND Kaiserslautern. 103 records from Außengelände KITA "Mäuseburg" Waldkirchen. 11 records from Desarrollar las actividades tendientes al manejo, conocimiento y conservación del Comino crespo (Aniba perutilis hemsl.), formuladas en el plan de conservación para la especie en el departamento del Meta. 22 records from Heilpflanzen im Hainbachtal. 129 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 57 records from Dorfrand Mauderode. 110 records from Obstwiese Osterberg. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 16 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 125 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 30 records from Artensuche auf den Elbwiesen in Radebeul. 56 records from Oschenberg, NO von Bayreuth-Laineck. 4 records from Schulbiotop und Brigach (Villingen). 26 records from Umgebung des Spalatin Gymnasium Altenburg. 97 records from Warnowtal (Rostock). 30 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 29 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 4 records from Goethe-Hauptschule/Projekt I-10. 96 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 85 records from Selztal bei Friesenheim. 88 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 296 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 84 records from Naturschutzgebiet Lochbusch-Königswiesen. 19 records from Uferzone Wipper (Biesenrode). 19 records from Breitkopfbecken (Berlin-Reinickendorf). 50 records from NSG Leist bei Ziegenhain. 30 records from Flächennaturdenkmal Grubditz. 40 records from Amtsrain Apolda-Zottelstedt. 149 records from Gieselbachtal Fulda-Harmerz. 42 records from Artenvielfalt auf der Wiese. 34 records from Saalewiesen Naumburg. 38 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 43 records from Schulgelände Thurmair-Gymnasium. 28 records from Hainbachtal bei Oelsnitz / V.. 34 records from Flora und Fauna am Mittelrheintal. 150 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 45 records from Schafsweide Seniorenhaus Berghof. 139 records from WildesMoor bei Schwabstedt. 94 records from Vielfalt verschiedener Wiesen. 47 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 53 records from Weidegut Rechab. 123 records from Binsenwiesen. 79 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 153 records from Bammentaler Duft- und Heilkräutergarten. 87 records from Grillhütte Wettsaasen, Wiese, Hecken. 46 records from Isartal Dingolfing. 117 records from NABU-Auerochsenweide. 53 records from Weidewirtschaft. 56 records from Birkenloh. 33 records from Kochertgraben II. 59 records from Dalbekschlucht. 49 records from Höltigbaum. 46 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 70 records from VFD-RP: Taunus: Ponykoppel Thurner. 111 records from Waldstück Bremerhagen LK Bio Kl. 12. 63 records from Hochschule Zittau/Görlitz. 73 records from Rund ums Cani. 34 records from GE-Brühl. 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 107 records from vegoek. 10 records from Neanderthal. 51 records from Naturerlebnisraum Koppelsberg (Plön). 1 records from Regenwasserabfangsbecken (Erlenbach). 16 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 85 records from Steinbruch Mainz-Weisenau, 3. Jahr. 84 records from Gelände des Schulzentrums am Himmelsbarg. 79 records from VFD-H: Heidenrod: Pferdeweide Mürth. 125 records from Biosphäre Bliesgau. 31 records from NABUGEO1. 10 records from Feuchtwiesen Wippertal bei Wippra. 8 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 6 records from Birdrace-Usedommeln-Ostvorpommern. 75 records from Leben im Finkensteiner Moor. 53 records from Wulfsmuehle/Pinnau. 30 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 37 records from Landschaftspark St.Leonhard-Deisendorf. 2 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 264 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 14 records from Zoo Frankfurt. 57 records from Industriebrache (Kempen). 4 records from Kurler Busch (Scharnhorst). 1 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 27 records from Schulgarten Fichteschule. 1 records from Schulgelände Kranich-Gymnasium (Salzgitter). 4 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 34 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 48 records from Kinderbauernhof Pinke-Panke. 31 records from LSG "Großes Bruch". 30 records from 8c. 1 records from Bach. 3 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 109 records from Römertal (Steinpleis). 35 records from Sternwiese Mülheim-Broich. 17 records from Naturerfahrung. 14 records from Steinbachtal (Würzburg). 28 records from Schulhof A.-Lindgren-Schule (Elmshorn). 22 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 71 records from Klütwald. 23 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 30 records from Park Schönfeld (Kassel). 36 records from Schulhof Liebfrauenschule Oldenburg. 29 records from Garten in Schmölln. 21 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 49 records from Schrebergarten Düsseldorf Oberkassel. 25 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 20 records from Mittelriede Höhe Gliesmarode-Braunschweig. 47 records from Dörnberg. 6 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 15 records from Schulgelände Ceciliengymnasium. 4 records from Regenwasserabfangbecken. 1 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 19 records from Schafheide im Böblinger Wald. 22 records from Regenrückhaltebecken Bad Bevensen. 56 records from Naturschutzgebiet Kochertgraben. 27 records from Streuobstwiese Haus Zeitz. 21 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 34 records from Gym Freyung. 7 records from Erhard Sopp. 53 records from Hoher Stein Kallenhardt. 23 records from Mühlenbach bei Buxtehude. 33 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 2 records from Tiere im Teichgebiet. 12 records from Bachabschnitt der Nette (Osnabrück). 5 records from Naturschutzgebiet Ahrschleife (Altenahr). 71 records from Draubiotop Lavamünd. 34 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 11 records from Waldgebiet Todtnau- Sonnhalde. 38 records from Schulgarten-St.-Georg-Gymnasium. 57 records from Mauervegetation,Flechten und anderes. 27 records from Estetal (Buxtehude). 12 records from Schulgarten der Hainbuchenschule (Hagenbach). 33 records from Issumer Fleuth. 8 records from Schulteich Heinrich-Mann-Schule. 23 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 10 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 17 records from Zwickau- Schwanenteich. 29 records from Nationalpark Harz Juniorranger. 5 records from Schulgelände Lise Meitner Realschule (Paderborn). 380 records from Sudeniederung (Amt Neuhaus). 62 records from Streuobstwiese. 2 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from Brenz (Heidenheim). 22 records from Ackerrain Plönhagen. 1 records from Glemstal (Leonberg). 2 records from Lerchenauer Baggersee (München). 23 records from Lahnufer in Villmar. 6 records from Kaisertal. 2 records from Wiese hinter der Schule (Darmstadt). 8 records from Kleiner Ziergarten Winzingen (Neustadt). 15 records from Kaltenkirchen Brache. 1 records from Mikroorganismen. 3 records from Tümpel Schulbiologiezentrum. 5 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 51 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 9 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 7 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 17 records from Salzwiese Diekskiel. 310 records from IBF Monitoring of Plant Galls. 13 records from FND "Weißer Berg" Leißling. 3 records from FFR Hausen. 38 records from Georgs-Padd (Wangerooge). 8 records from Warnowufer Groß Klein. 5 records from Im und um das Schulhaus. 1 records from LBV-Kindergruppen Markt Tussenhausen. 3 records from Wattuntersuchung (Cuxhaven). 2 records from Wattenmeer-Safari (Wurster Watt). 19 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 9 records from Kleinstbiotop mit Schulteich/Weißwasser. 5 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 13 records from Nachtaktiv im Ökogarten (Bad Waldsee). 4 records from Privatteich(St.Leon). 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 23 records from Tiere und Pflanzen um uns herum !. 37 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 2 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 2 records from Tauchen und Meer. 1 records from Bachpatenschaft Beeke. 8 records from Ohemoor (Hamburg/Norderstedt). 2 records from Sächsische Schweiz (Wehlener Gebiet). 3 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 47 records from Landschaftsschutzgebiet Buchhorst 4. 31 records from Schulteich Freie Waldorfschule Darmstadt. 8 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 3 records from Stadtrandlandschaft Apolda-Nord. 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 27 records from Rotes Steigle (Panzerübungplatz Böblingen). 5 records from Schulinnenhöfe (Gelsenkirchen). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 53 records from Waldi-Weiher. 4 records from Schulhof Montessori Schule (Rotenburg / Wümme). 1 records from Haslauer Moor. 96 records from Tiere und Pflanzen am Pfannenbach. 1 records from Karpfenteich, Klasse 6d. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 206 records from FFH-Gebiet "Calwer Heckengäu". 70 records from Schulgelände Paul-Gerhardt-Schule. 44 records from Landschaftsschutzgebiet Schmutterwald. 53 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 623 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 204 records from Bannwald Burghauser Forst. 81 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 135 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 169 records from Rohrmeistereiplateau und angrenzendes Gebiet. 31 records from Fürstenberger Ralley Teil 3. 58 records from Müritz-Nationalpark. 60 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 215 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 281 records from Pöhlberg bei Annaberg. 57 records from Kaniswall/ Gosener Wiesen an der Spree. 126 records from Expedition "Schulgelände". 581 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 63 records from Haarbach Höfe. 305 records from Schulzentrum "Parc Hosingen". 80 records from LK 11 im Mönchspark. 49 records from Schulwald Grundschule Brügge. 134 records from Bernhardsthal. 89 records from VFD-RP: Taunus: Kirchenweide Köpplers. 103 records from VFD-RP: Eifel: Orchideenweide Ankly. 220 records from Weinberg Reichersdorf. 77 records from Schulwald Marksuhl. 1 records from BIRDRACE Gätkes Erben. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 1 records from BIRDRACE Guckers Offenbach. 1 records from BIRDRACE Oostfreesland Bird-Lopers. 1 records from BIRDRACE Unterste Niederrhein-Rennvögel. 60031 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 2 records from BIRDRACE Immerwiederhopf. 162 records from Naturschutzgebiet Börstig bei Hallstadt. 199 records from Tag der Artenvielfalt in Heidelberg. 31 records from Wiesen am Treffpunkt Freizeit. 44 records from Tongrube bei Hettstedt. 2 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 42 records from FFH-Gebiet Klosterwasser/Burkau. 60 records from Gronau - auf der Suche nach dem Neunauge. 43 records from Langes Tannen(LMS), Klasse 5d. 19 records from Liether Park 2 (LMS), Klasse 6c. 271 records from Schatzinsel Wangerooge. 128 records from Lustbach-Umland. 31 records from Königsdorfer Wald. 60 records from VFD-HH/SH: Pferdweide Lammert. 101 records from Owere Fiddel. 8421 records from BioMar - LIFE project. 43 records from Hettstadt Gehäge. 95 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 334 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 75 records from Tornoer Teich. 143 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 54 records from VFD-H: MIttelgebirgsweide. 51 records from Biotope im Schulumfeld. 48 records from Streuobstwiese Stedar. 61 records from Liether Kalkgrube. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 110 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 35 records from Lebensraum Dorf. 202 records from Schulgarten der Volksschule. 81 records from Sürther Aue. 79 records from Feldweg Waldkirchen. 88 records from Aachtobel. 123 records from Bodenteicher Seewiesen. 208 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 40 records from Wälder im Hainbachtal. 76 records from Steinbruch Kronungen. 46 records from Ober-Olmer Wald. 54 records from Rund um den Hainbergsee. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 66 records from "Ahrschleife bei Altenahr". 170 records from Pflanzen und Tiere im Burgwald. 33 records from Wir erkunden die Hofau, Klasse 5c. 18 records from Waldwiese. 9 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 44 records from Von der Nutzung zur Natur. 48 records from VFD-H.: Rheingau: Bärstadt. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 22 records from Liether Park 1 (LMS), Klasse 5b. 1 records from BIRDRACE Die Schwenker-Birder. 10 records from Landschaftsschutzgebiet Buchhorst2. 1 records from Schulgarten Waldorfschule Hassfurt. 22 records from Unter hellen Zinnen und finsteren Grotten. 26 records from FFH-Gebiet Paartal. 8 records from Schulgarten Janusz-Korczak-Realschule. 25 records from Geführte Wanderung im Eselsbachtal. 16217 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 8 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 32 records from Wahner Heide LK 12 Biologie. 42 records from Aktion der Klasse H2 in Simmelsberg. 84 records from VFD HH/SH "Pferdeweide Lemsahl". 28 records from Schüler erforschen die Helme-Aue. 5749 records from NX - Herbário Nova Xavantina. 32 records from Rosarium (LMS), Klasse 6a. 7 records from Leben auf einer Sturmfläche. 25 records from Reusaer Wald. 36 records from Rechts des Inn Höhe Hofau Rosenheim. 29 records from Schulgarten Zinnowwald-GS. 10 records from Feuchtwiese Grüne Mitte, Klasse 5a. 72 records from Teich im Wald zwischen Böblingen und Schönaich. 16 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 9 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 9 records from Riekdahler Wiesen. 13 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 17 records from Höhle am Neuweg / Sächsische Schweiz. 42 records from Kindervilla Außengelände. 4 records from Flora und Fauna am Mühlberg. 76 records from VFD-RP: Taunus: Mähweide Dehe. 123 records from "Schwarzwassertal" bei Pobershau. 1 records from Streuobstwiese Alt Necheln. 2451 records from Alga (NSMK-AG). 2741044 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 10 records from Monitoring of Nigritella nigra in the Kvikne mountains, Tynset, Norway. 2986 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 798 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 66 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 2 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 731 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 12329 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 1 records from bugland. 8070 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 2252 records from Hawaiian Algal Database. 3777 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 10666 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 28 records from Chrysomelidae of Poland. 8 records from Biodiversity records from Ireland - general. 215 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 34 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 27 records from Diveboard - Scuba diving citizen science observations. 8 records from CM Vertebrate Paleontology Collection. 182502 records from Bryophyte herbarium, Trondheim (TRH). 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 7621 records from Bryophyte collection of Porto Herbarium (PO). 49781 records from Continuous Plankton Recorder Dataset (SAHFOS). 249236 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 56 records from Illinois Natural History Survey Insect Collection. 566 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 5389 records from Ireland's BioBlitz 2012. 65321 records from OAC-BIO Herbarium. 22853 records from Bryophyte herbarium, Oslo (O). 24573 records from VIC - Herbário da Universidade Federal de Viçosa. 8420 records from Polish seed gene bank – historical passport data of accessions. 2421 records from Census of plant species in Toffo forest reserve. 754 records from Inventaire National du Patrimoine Naturel : CBN Méditerranéen de Porquerolles. 1553 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 1054 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 155 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 2300 records from Botanical Society of the British Isles - Demonstration set of data downloaded from the BSBI threatened plant database. 117 records from (Appendix B) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB1105-4. 691 records from Naturalis Biodiversity Center (NL) - Diptera. 30 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 54398 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 21 records from Distribution of palynomorphs in surface sediments of the Laptev Sea. 114 records from Spores and dinoflagellates of Site 175-1075. 100 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 22 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 88 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 3 records from Phytoplankton counted in three surface sediment samples from the South Atlantic at station PS2230-1, PS2367-1 and PS2376-2. 279 records from SMNS Palaeontological collection - Invertebrates (Jurassic and Cretaceous). 54 records from Calcareous dionoflagellate cysts from surface sediments. 55228 records from Herbario de la Universidad de Granada: GDA. 41 records from (Table 2) Dinoflagellate cysts in surface sediment samples of Meteor cruises M20/2, M23/1, M34/2 and M34/2. 12 records from Dinoflagellate cysts of mooring MST-8 (station 905), full and empty cysts. 23 records from Dinoflagellate cysts of mooring MST-9 (station 915), full and empty cysts. 1 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 32 records from Dinoflagellate cyst counts on sediment core ABC26. 205 records from Dinoflagellate cyst countings of sediment core MD95-2002. 131 records from Dinoflagellate cysts counts of sediment core MD95-2010. 222 records from Dinoflagellate cysts counts of sediment core MD95-2042. 470573 records from naturgucker. 14100 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 23 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 380 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 127 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 233 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 103 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-175-1. 25448 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2954 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 3 records from Outer Hebrides Biological Recording Project - OHBRP Fungi, Lichens and Lower Plants Dataset - Outer Hebrides. 864 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 4 records from Phytoplankton abundance in surface water during cruise CD60. 37 records from Phytoplankton abundance in surface water during cruise CD61. 1 records from Phytoplankton abundance at station CD46_1005C#4. 1 records from Phytoplankton abundance at station CD46_1305C#2. 1 records from Phytoplankton abundance at station CD46_2005C#4. 3 records from Phytoplankton abundance at station CD47_0306C#7. 5 records from Phytoplankton abundance at station CD47_0606C#7. 1 records from Phytoplankton abundance at station CD47_0906C#6. 4 records from Phytoplankton abundance at station CD47_1206C#7. 1 records from Phytoplankton abundance at station CD47_2805C#5. 1 records from Phytoplankton abundance at station CD47_3105C#4. 1 records from Phytoplankton abundance at station DI182_11864#61. 1 records from Phytoplankton abundance at station DI183_11872#3. 3839 records from Dataset of Global Change, altitudinal range shift and colonization of degraded habitats in mediterranean mountains (MIGRAME). 28 records from Erik Acharius lichen collection. 20 records from (Table 3) Dinoflagellate cysts from sediment profile PS1730. 24 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 8 records from Phytoplankton abundance at station Sechin_EP1 in 2002, Casma, Peru. 43 records from Phytoplankton abundance at Station Sechin_EP2 in 2002, Casma, Peru. 163 records from Entomological collections, UiB. 2 records from Phytoplankton abundance at station Casma_2003-06-24_1, Casma, Peru. 1 records from Phytoplankton abundance at station Casma_2003-06-24_2, Casma, Peru. 19 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1756-5. 45 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1768-8. 54 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 2 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 1 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 2 records from Phytoplankton abundance at station Sechin_2003-08-06_1, Casma, Peru. 1 records from Phytoplankton abundance at station Sechin_2003-08-06_2, Casma, Peru. 2 records from Phytoplankton abundance at station Sechin_2003-08-27_1, Casma, Peru. 1 records from Phytoplankton abundance at station Sechin_2003-08-27_2, Casma, Peru. 1 records from Phytoplankton abundance at station Sechin_2003-11-25_1, Casma, Peru. 1 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 7421 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 87 records from Dinoflagellate cyst counts of sediment core GIK23071-3. 61 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 817 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 1 records from Lice (Phthiraptera) of Ireland. 9 records from Vigna pandeyana (Fabaceae), a new species from northern Western Ghats, India. 4129 records from Rye, Barley, Oats Genetic Resources. N.I.Vavilov Research Institute of Plant Industry, St. Petersburg. 22113 records from West-, Central- and East African Plants Databases. 10067 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 284 records from Botanical collection of the National Museum. 155 records from The Distribution Atlas of Butterflies in Poland. 4805 records from National Trust - Hatfield Forest species data held by The National Trust.. 77775 records from Scottish Natural Heritage - Standing Waters Database. 3161 records from Census in Agrimey forest reserve (southern Benin). 7122 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 9 records from (Table 2, 3) Macro- and meiofaunal specimens abundance, organic carbon content and analysis of coarse clasts of box core samples from the North Pacific Ocean. 5 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 4340 records from R-Criptogamos - Herbário do Museu Nacional - Criptogamos. 11185 records from Registros biológicos del género Piper en el herbario HUA. 12 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Northwest African upwelling area. 103 records from Scottish Environment Protection Agency - Scottish river macro-invertebrate records from 2007 collected by SEPA. 1911 records from UTEX Culture Collection of Algae at The University of Texas Living Algae Holdings. 928 records from Natural England - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by English Nature. 307 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 39 records from Benthos counted on dredged samples during Valdivia cruise VA44. 77 records from Benthos counted on dredged samples during Valdivia cruise VA53. 480 records from Freiburger GEO-Tag der Artenvielfalt. 10 records from Sandloch - Höhle. 590 records from Biosphärenpark Wienerwald - Pfaffstätten. 205 records from Kühmark bei Wetzlar. 175 records from Eschlberg Thalhausen. 522 records from GEO-Hauptveranstaltung in "Wildtierland". 68 records from Sahrbachtal Kreis Ahrweiler. 72 records from Schulgelände des Schulzentrums am Himmelsbarg. 122 records from Baggerseen bei Krauchenwies. 21 records from Schulaktion des Dienzenhofer-Gymnasiums. 30 records from Schriesheimer Steinbruch. 29 records from Artenvielfalt in der Kinderakademie im RFZ. 2 records from Die Bachspezies 2008/2009. 25 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 3 records from Ökosysteme rund um Wedel. 99 records from Mangfalltal. 4 records from "Am Riedert" im Westerzgebirge. 2 records from Wälder und Seen rund um den Mühlenberg. 29 records from GEO-Tag am Hohlen Stein. 504 records from LBV 100 - Artenvielfalt am Rothsee. 4 records from Grünanlagen Stadt Brandenburg an der Havel. 3 records from Zwischen Enz und Schule. 36 records from Naturpark Kottenforst-Ville 18.6.09. 86 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 216 records from Bayerische Donau - Leipheim. 61 records from Aktion - Friedensburg Oberschule. 27 records from Koleopterologen am Bausenberg. 145 records from Artenvielfalt im Rhein-Neckar-Raum. 6 records from Aktion des Romain-Rolland-Gymnasiums. 23 records from Artenvielfalt auf Zollverein. 329 records from Schatzinsel Norderney. 135 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 170 records from Biotope in Rheine - Aktion 350. 99 records from Artenvielfalt am "Grünen Band" bei Coburg: 20 Jahre Wiedervereinigung. 316 records from Schanzenanlage Bergham. 92 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 266 records from Dornwanger Moos. 68 records from Die Teiche im Britzer Garten. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 232 records from Butterberg, Dardesheim. 2 records from Kleinod unter Hochspannung. 5 records from Tuttlinger Tag der Artenvielfalt. 33 records from Naturpark Kottenforst-Ville 15.6.09. 29 records from Liether Park (LMS), 6g. 61 records from Nationalpark Jasmund. 387 records from Bulau. 187 records from Luderbusch. 83 records from Werl macht sich auf die Suche. 77 records from Schulgarten Zinnowwald-Grundschule. 5 records from Wiese. 5 records from Wanninchen. 5 records from Schulwald Regionale Schule Sprendlingen. 46 records from Rur. 377 records from Inventory of Niaouli forest (South-Benin). 36 records from Parkuntersuchung Weißer See. 25 records from Feuchtbiotop Weidenkaule. 1 records from Haselbachtal. 51 records from Mönchspark. 246 records from Wälder bei Nordkirchen. 67 records from BB-Biodiversität b. 248 records from Projekt Dellbrücker Heide. 1 records from Kirchenforst. 24 records from Naturpark Kottenforst-Ville 19.6.09. 56 records from Rund um die Sausenburg. 103 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 325 records from Bayerische Donau - Blindheim Donaubrücke. 48 records from Streuobstwiese Stedar 2008. 122 records from Schloss Fasanerie Eichenzell. 81 records from Donauinsel des BN bei Entau. 76 records from Streuobstwiese Stedar 2009. 24 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 43 records from Feuchtwiese in Langes Tannen (LMS), Klasse 5c. 19 records from Liether Park (LMS), 5a. 17 records from Liether Park (LMS), 6c. 22 records from Liether Park (LMS), 6b. 79 records from Schiller Gymnasium Hof 10b. 85 records from Schieferbrüche. 36 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 35 records from Reifrocknarzissenwiese Löcknitz. 34 records from Schulhofuntersuchung Thomas-Mann-OS. 35 records from Lebensraum Walram. 1 records from Wildnis Sturmschaden. 72 records from Artenvielfalt des "Grünen Klassenzimmers". 22 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 1 records from Heckenstreifen am Zehntbergweg. 177 records from Naturpark Sternberger Seenland. 3 records from Trockenwiesen und angrenzender Waldrand im Hainbachtal. 2 records from Wie viel Natur gibt es im Park?. 26 records from Stadtwald Heide. 115 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 35 records from Listhof und Umgebung. 29 records from Naturpark Kottenforst-Ville 16.6.09. 35 records from Naturpark Kottenforst-Ville 17.6.09. 61 records from Raus in die Natur. 52 records from Rund ums Schulgelände. 18 records from Naturnachmittag 'Artenvielfalt an der Ecke' (Wäldchen an der Wegegabelung). 146 records from Bayerische Donau - Neu Ulm. 25 records from NABU-Fläche am Bösselhausener Weg. 86 records from Exkursion Ebertsheimer/Grünstädter Berg. 85 records from Binsenwiesen im Bizzenbachtal. 91 records from Pfingstexkursion Alter Bessin. 107 records from Oberes Schindelbachtal. 76 records from Artenvielfalt vor unserer Kita-Haustür. 29 records from BB-Biodiversität a. 36 records from Seeufer ehem. BUGA-Gelände. 1 records from Wirtschaftsgrünland, Intensiv genutze Wiese. 28 records from Leben in den Elbwiesen. 22 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 42 records from Wiesen in der Grünen Mitte. 12 records from Bilder der Natur. 97 records from Artenvielfalt und Kulturlandschaft. 380 records from Naturschutzgebiet Lüneburger Heide. 51 records from Dalbek-Schlucht. 35 records from Aktion Wiese und Wegrain Gitzenheide. 47 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 1 records from FTEA. 1000 records from Plant specimens of Natural History Museum, Kishiwada City. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 3415 records from Plant Specimens collections of the Kyushu UNniversity Museum. 55 records from MfN - Fossil invertebrates Ia. 4 records from MfN - Trace fossils. 175 records from MfN - Fossil invertebrates IIb. 20 records from MfN - Fossil invertebrates III. 1 records from MfN - Fossil vertebrates IV. 16125 records from MfN - Fossil plants (Cenophytic). 7711 records from MfN - Fossil plants (Mesophytic). 12759 records from MfN - Fossil plants (Paleophytic). 1 records from MfN - Fossil vertebrates II. 3 records from MfN - Fossil plants II. 1 records from Mammal Collection. 2341 records from Tullie House Museum - Tullie House Museum Natural History Collections.. 890 records from Red list project inventory, vascular plants. 4 records from Phytoplankton abundance at station DI182_11862#3. 1720 records from KTU Pinophyta. 15896 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 435 records from Community dynamics in a species-rich patch in the Brazilian Atlantic Forest near Viçosa/MG. 175119 records from The Flora of County Wexford. 8853 records from Vascular Plants Collection of National Museum of Nature and Science. 334 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 16 records from (Table 1) Species abundance at DSDP Hole 63-467. 2382 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del piedemonte de Arauca, municipio de Tame. 19945 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 9694683 records from Dutch Vegetation Database (LVD). 1148 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 26237 records from Bolus Herbarium Specimens Collection (1865-2009). 492 records from Plant (HBBG-PL). 757817 records from Flora Atlas N.T.. 20998602 records from INPN - Données flore des CBN agrégées par la FCBN. 219 records from INERA-Luki reservation herbarium (CABIN project). 3770 records from Herbier de Wallis et Futuna. 183 records from Merseyside BioBank - Merseyside BioBank NBN Frequently Updated Taxa. 684 records from seed. 11374 records from EFC - Herbário Escola de Florestas Curitiba. 34270 records from ASE - Herbário da Universidade Federal de Sergipe. 152501 records from UEC - Herbário da Universidade Estadual de Campinas. 60 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 33318 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 2133 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 3 records from UWBM Herpetology Collection (Arctos). 12673 records from Colección Nacional de Paleobotánica - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1267400 records from New Zealand National Vegetation Survey Databank. 2377 records from Rådgivende Biologer. 919 records from BioBlitz Barcelona 2010-14. 2779 records from Museu Paraense Emílio Goeldi - Herbarium Fanerógama Collection. 52555 records from FUEL - Herbário da Universidade Estadual de Londrina. 19145 records from Environment Agency - Environment Agency Non-native Species records v1. 1 records from MSB Parasite Collection (Arctos). 3 records from Benthic macrofauna abundance of subcores of sediment core 13200-045. 41 records from Abundances of organic-walled dinoflagellate cysts in sediment core GeoB5546-2. 7 records from Northern Territory Museum and Art Gallery provider for OZCAM. 39 records from New records for Albania based on taxa from the Prespa National Park. 9 records from Bats of Poland. 25 records from Dinoflagellate cysts from sediment core PS1295-4. 66 records from Dinoflagellate cysts from sediment core PS2138-1. 3 records from Dinoflagellate cysts from sediment core PS2458-4. 19 records from Dinoflagellate cysts from sediment core PS2471-1. 36 records from Dinoflagellate cysts from sediment core PS2741-1. 9 records from Dinoflagellate cysts from sediment core PS2757-8. 17 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 3 records from (Table 4b) Calcareous nannofossil distribution on ODP Hole 117-721B. 2 records from (Table 6a) Calcareous nannofossil distribution on ODP Hole 117-731A. 421235 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 1080 records from AlgaTerra. 60058 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 163249 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 4688 records from Herbario del Departamento de Biología Vegetal (Botánica) de la Universidad de La Laguna, Tenerife (TFC). 159239 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 9610 records from Colección de Monocotiledóneas Mexicanas (UAM-I). 1100 records from Pinos del Noreste de México (UANL). 486 records from Colección de Flora Ficológica Marina de Tamaulipas, México (UANL). 1424 records from Hertfordshire Biological Records Centre - Hertfordshire Lowland Meadow Inventory Survey 2010. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 38476 records from Herbario del CIBNOR. 34 records from The national database for marine data (MADS). 1667 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 1343 records from Bryophyte specimens of Iwate Prefectural Museum. 46003 records from Vascular plant specimens of Akita Prefectural Museum. 26863 records from Vascular plants database of Atugi City Museum. 1 records from Collection Crustacea NHCY. 329 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 4 records from Bayerische Donau - Etterzhausen. 60 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 10 records from Bayerische Donau - Riedlingen. 24583 records from Jardin botanique de Montréal (JBM). 13 records from Bayerische Donau - Tapfheim. 112 records from Artenvielfalt rund um die Dalbek-Schule. 48 records from Biosphärenreservat Mittelelbe. 8421 records from BioMar - LIFE project. 1 records from Biotop Alexander-von-Humboldt-Schule. 1 records from "Schule am Inselsee" Güstrow. 14 records from Exkursion in der Ehrbachklamm/ an den Erbach. 2 records from Familientag am Schorberg. 11 records from Feuchtbiotop Otto-Hahn-Gymnasium. 1 records from Der Kreuzenzian und sein Bläuling. 8 records from 2. Aspacher GEO-Tag der Artenvielfalt. 2 records from 2. Donauinsel bei Entau. 52 records from Fliegenhaupt Marksuhl. 2540 records from Marchantiophyta / Hepatics / Liverworts of Russian Fennoscandia. 35 records from Flora und Fauna im Brexbachtal. 10 records from Fluss - Vielfalt. 56 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 118 records from Grünes Germersheim. 2 records from Grünfläche Forckenbeckplatz. 31 records from Kindervilla Aussengelände/ Hiltroper Park. 1 records from LUNG-Naturwiese. 174 records from Neißetal. 48 records from Ober-Olmer Wald 09. 1 records from Parthenaue. 7444 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 1 records from Regenwasserabfangbecken Erlenbach. 1 records from Schneifelkinder erkunden südliche Blumenpracht. 10 records from Schulteich Regionales Förderzentrum "J.H. Pestalozzi" Sondershausen. 53 records from Schulwald Sprendlingen. 10 records from Steinbruch Mainz-Weisenau, 4.Jahr. 73 records from Sukzession Industriebrache. 8 records from TBW-Schafberg. 2 records from Tauchaktion. 1 records from Vogelwelt im Europa-Rosarium. 9 records from Volkspark Prenzlauer Berg. 13 records from Wasser-Lernort Nettemündung. 3 records from Wasserbachsee. 43199 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 101116 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 45896 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 437 records from Gymnospermatatophytina Collection of Saitama Museum of Natural History. 2777 records from Bryophyta Collection of Saitama Museum of Natural History. 7342 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 2453 records from Amphibian and Reptile (NSMK-AR). 128 records from Marine Plants (NHMC-SA). 319 records from Fossil (WSHN-FO). 998 records from Plant (KOBG_PL). 108 records from Fossil (NSMK-FO). 5476 records from Plant (KIWE-PL). 13589 records from Plant (JNHM-PL). 8 records from Birds (JNHM-BI). 1 records from Insect (HUNM-IN). 984 records from Plant (HBBG-PL). 3848 records from Plant (MNHM-PL). 289 records from Plant (SMNH-PL). 3755 records from Plant (NHMC-PL). 2345 records from Coimbra Collection of Algae. 4 records from Insect (JNHM-IN). 4 records from Insect (MNHM-IN). 1016 records from Alga (KIWE-AG). 3909 records from Plant (GFEI-PL). 13 records from Shellfish (NSMK-MS). 354 records from Fossil (GNHM-FO). 82840 records from Plant (NSMK-PL). 986 records from Plant (NHMK-PL). 400 records from Fossil (MNHM-FO). 1969 records from Plant (JJHA-PL). 184 records from 녹조류 DB. 81190 records from Herbaria of the University and ETH Zürich. 2061 records from Bryophyte collection of Jyväskylä University Museum. 1277 records from Mongolian Plant (MMNH-PL). 10928 records from TRTE Herbarium (TRTE). 609 records from Collection botanique Mulon L. (BOUM). 27828 records from svalbardflora.net. 110 records from South American Antarctic Marine Biodiversity Literature. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 3165 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Santuario de Flora y Fauna Los Colorados. 2 records from Collection Oligochaeta - ZIM Hamburg. 1 records from Collection Polychaeta - ZIM Hamburg. 1 records from Collection Hydrozoa - ZSM München. 10 records from Collection Crustacea - ZMB. 6 records from Collection Vermes - ZMB. 96461 records from Tiroler Landesmuseum Ferdinandeum. 2625 records from The Fungal Collection at the Botanische Staatssammlung München. 25369 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 394744 records from IBF Monitoring of Vascular Plants. 1400 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 215 records from IBF Monitoring of Lichens. 1 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 342 records from IBF Monitoring of Fungi. 1485 records from The Lichen Collection at the Botanische Staatssammlung München. 652 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 28 records from BIOTA Southern Africa - The Collection of Lichens at the Botanische Staatssammlung München. 7505 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 12 records from Landwehrbach. 7829 records from Universidad Autónoma de Madrid, Biología, Acalypha. 2077 records from Vascular plant specimens of Iida City Museum. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE262. 65 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 78 records from (Figure 3) Range chart of dinocysts of ODP Hole 104-643A. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE255. 12 records from (Figure 6) Range chart of dinocysts of ODP Hole 104-642C. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE258. 23 records from (Table 3) Dinocyst ranges in ODP Hole 104-642D. 16 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE241. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 4 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE218. 342627 records from BSBI tetrad data for Ireland. 44 records from (Figure 7) Range chart of selected dinocysts and acritarchs of ODP Hole 104-643A. 64 records from (Figure 6) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642C. 71 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 1586 records from Marineplant (JBRI-SA). 4437944 records from Tropicos Specimen Data. 140 records from (Figure 8) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 15-35. 128 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 12 records from (Appendix A) Dinoflagellate cyst analysis of surface sediment samples off West Africa. 15 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 1 records from Coleoptera Collection. 81 records from (Table 2) Distribution of dinoflagellate cycst in OFP Hole 123-765C. 12 records from (Table 2) Percent distribution of calcareous nannofossils at ODP Hole 125-782A. 4 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE278. 1 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 31 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 1534 records from Pontaurus. 4753 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 265 records from AIS Wildtype Populations of Arabidopsis. 12 records from (Table 3) Distribution chart of dinoflagellate cysts and acritarchs from DSDP Hole 27-263. 180 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 39 records from Dinoflagellate cyst species composition of recent surface samples (Appendix). 7 records from (Table 2) Median abundances of macrobenthos in surface sediments. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 3005 records from Annotated Atlas of the Vascular Flora of Macquarie Island - 1979. 16 records from (Table 3) Distribution of dinoflagellate cysts in ODP Hole 103-641A. 102 records from EDIT - ATBI in Spreewald (Germany). 5298 records from Caracterización del hábitat de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 18 records from SysTax - Zoological Collections. 32 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 32 records from (Table 1) Stratigraphic distribution of new marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE275. 18 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 21 records from Palynomorph concentrations in ODP Hole 105-645B samples (Table 1). 11 records from (Table 1) Palynomorph concentrations in ODP Hole 105-646B samples. 14 records from (Appendix 2) Late Cretaceous benthic foraminifera of ODP Site 207-1259. 1001 records from Naturhistorisches Museum Mainz, Botanical Collection. 1 records from Naturhistorisches Museum Mainz, Zoological Collection. 2372 records from CeDoc de Biodiversitat Vegetal: BCN- Algues de J. Rodríguez Femenías. 7312 records from Botanical Research Intitute of Texas. 575654 records from Natural History Museum (London) Collection Specimens. 870 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Corynephorus canescens domiated grassland. 6 records from (Table 7) Dinoflagellate cyst species distribution in ODP Hole 112-680B. 7 records from (Table 6) Dinoflagellate cyst species distribution in ODP Hole 112-679D. 12 records from Chenopodieae. 14 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 7 records from (Table 8) Dinoflagellate cyst species distribution in ODP Hole 112-681B. 6 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 7 records from (Table 10) Dinoflagellate cyst species distribution in ODP Hole 112-686B. 7 records from (Table 11) Dinoflagellate cyst species distribution in ODP Hole 112-687B. 11 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2007. 9 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 9 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 14 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 105522 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 4267 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 4 records from Bumblebees, cuckoobees and butterflies in southern Poland. 102 records from Clitellata - SMF. 75418 records from Botanical Museum, Copenhagen, the Phycology Herbarium. 288889 records from Natural History Museum, Vienna - Herbarium W. 9 records from Occurrences des observations de la campagne Suivi Aérien de la Mégafaune Marine en France métropolitaine (SAMM1 - Hiver 2011/2012). 5291 records from Inventario de Flora y Vegetación del Municipio de Enguídanos (Cuenca), 2010. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 3 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 431 records from Sistemática del género Polianthes L (Agavaceae). 84 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 1636 records from Flora útil del Municipio de la Huerta, Jalisco. 6724 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 1215 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 458 records from Revisión taxonómica del género Furcraea (Agavaceae) en México y Guatemala. 6454 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 571 records from Catálogo de autoridad taxonómica del género Quercus, Fagaceae en México. 503 records from Inventario fitopatológico de las especies vegetales dominantes en la región de Zapotitlán de las Salinas, Pue.. 1 records from Hongos del estado de Veracruz. 3996 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 727 records from Flora acuática vascular del área focal Felipe Carrillo Puerto, Corredor Biológico Sian Ka'an-Calakmul, Quintana Roo, México. 1814 records from Inventario florístico de la Sierra de San Carlos, Tamps. 4412 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 1729 records from Biodiversidad de Datura (Solanaceae) en México. 120 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 228 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Plantas vasculares. 2074 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 1503 records from Diversidad florística y endemismo en la Reserva de la Biósfera El Cielo, Tamaulipas, México. 17 records from Sistematización de la Colección Paleontológica de la Facultad de Ingeniería, UNAM. 1182 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 7926 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 7182 records from Lista florística preliminar de Tamaulipas. 1734 records from Flora de macroalgas del litoral oaxaqueño. 1336 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 1351 records from Pteridoflora de Morelos. 7503 records from La familia Asclepiadaceae en México. 200 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 4565 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 251 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 654 records from Estudio sistemático y ecológico del género Tigridia (Iridaceae). 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 4317 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 78 records from (Table T2) Dinoflagellate stratigraphy of ODP Hole 184-1148A. 1893 records from Las especies endémicas de plantas en el estado de Jalisco, su distribución y conservación. 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 26 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1599 records from Florística de la reserva de la biósfera de Mapimí. 565 records from Flora vascular del cerro El Zamorano. 3060 records from Composición florística del Parque Nacional Huatulco. 870 records from Contribución al conocimiento de la flora útil de la selva Lacandona. 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 2543 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 874 records from Flora acuática de Querétaro. 801160 records from NatureServe Network Species Occurrence Data. 1 records from Computarización del Herbario ENCB, IPN. Fase IV. Base de datos de la familia Pinaceae y de distintas familias de la clase Magnoliopsida depositadas en el Herbario de la Escuela Nacional de Ciencias Biológicas, IPN. 929 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 6448 records from Catálogo para la utilización, conservación y disponibilidad de Phaseolus en México. 337 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 12613 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 253507 records from Flora-On: occurrence data of the flora of mainland Portugal. 237 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 55 records from Niveles y patrones de variación genética del género Abies en México. 202 records from Diversidad y conservación del germoplasma de henequén Agave fourcroyedes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 476 records from Investigaciones sobre recursos no maderables de México: biología evolutiva y conservación de plantas del género Chamaedorea. 900 records from Lothian Wildlife Information Centre - Lothian Wildlife Information Centre Secret Garden Survey. 1310 records from Inventario ficoflorístico de las comunidades arrecifales del Parque Nacional Bahías de Huatulco, Oaxaca. 500 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 2401 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 412 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Bosques. 290 records from Diversidad y distribución de las comunidades de fitoplancton de ríos y lagunas del volcán San Martín de la reserva de la biósfera Los Tuxtlas. 654 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 1756 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 933 records from Flora de las Barrancas del Cobre. 786 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 118 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 6675 records from Estudio taxonómico y base de datos del género Muhlenbergia de México. 1613 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 1540 records from Inventario nacional de especies vegetales y animales de uso artesanal. 168 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Acahuales. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 40 records from Potencial económico de la flora útil de los cafetales de la Sierra Norte de Puebla. 1240 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 4603 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 3817 records from Manual de las gramíneas de Durango. 11779 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 900 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 1038 records from Plantas exóticas del centro de México y obtención de imágenes para una flora virtual de malezas. 2340 records from La etnobiología de los recursos nutritivos en las comunidades Tzeltales en los Altos de Chiapas. 1 records from UAM Insect Collection (Arctos). 50 records from Conocimiento de la macroflora marina de interés económico de las Costas de Yucatán. 356 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1740 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Nectar. 297 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 19156 records from Ireland's BioBlitz. 682 records from Banco de información sobre características tecnológicas de maderas mexicanas. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 704 records from Biodiversidad de productores primarios de lagunas costeras del norte de Yucatán, México_1. 2076 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 129896 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 269 records from Patrones de variación espacial y temporal de la biodiversidad fitoplanctónica de los cenotes abiertos de Yucatán. 3527 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 10500 records from Formación del banco de datos del herbario (UCAM). 53 records from Distribución e inventario de algunas especies bentónicas (hexacorales, octocorales, esponjas, y especies misceláneas) en arrecifes del Caribe mexicano. 1032 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 7310 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 3004 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 3558 records from Recuento de la diversidad florística de Veracruz. 2399 records from Estudio monográfico de la familia Rhamnaceae en México. 2765 records from Estudio biosistemático del género Bouteloua (Poaceae) en México. 2091 records from Estudio florístico de las gramíneas de Zacatecas. 3256 records from Florística de áreas protegidas en el estado de Durango. 8574 records from Base de datos sobre la flora de Durango. 1218 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 3253 records from Inventario florístico de la Sierra de Huautla, Morelos. 2379 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 5 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 12077 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 1034 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 625 records from Inventario de la biota terrestre (florístico) del parque nacional Isla Isabel. 33274 records from West African Vegetation Database. 7208 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 813 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 1526 records from Brioflora de la Reserva de Montes Azules, Chis.: Diversidad, biogeografía y depauperación por actividad humana. 2814 records from Flora acuática vascular y de zonas inundables del área de protección de flora y fauna Laguna de Términos, Campeche, México. 3055 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 1032 records from Flora y vegetación de la Sierra de San Carlos en el municipio de San Nicolás, Tamaulipas. 104 records from Inventario de la biota marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 10 records from Programa de erradicación de los roedores introducidos en la Isla Rasa, Baja California: un plan de restructuración ecológica. 7503 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 4529 records from Flora Novo Galiciana-Gramineae. 500 records from Plant Specimens of Oiso Municipal Museum. 8 records from UAM Invertebrate Collection (Arctos). 14202 records from Plant specimens of Hokkaido University Museum. 6912 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 8784 records from Bryopytes specimens of Akita Prefectural Museum. 5 records from Bryophyte Collection of Shizuoka Prefecture Museum of Natural History. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 941 records from Pteridophyta specimens of Iwate Prefectural Museum. 21129 records from Pteridophyta specimens of Shizuoka Prefecture Museum of Natural History. 105 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees - Fitoplancton de lagos pirenaicos. 117 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 4688 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 273 records from Herbarium of Lars Levi Laestadius. 57 records from Harold W. Manter Laboratory of Parasitology Collection. 310 records from KNWR Herbarium Collection. 2750 records from Botanical specimens database of Mr. Jiro Ito collection, Shizuoka Prefecture Museum of Natural History. 3724 records from Ibaraki Nature Museum, Bryophyta collection. 4310 records from Ibaraki Nature Museum, Algae collection. 115245 records from Dataflos. 75655 records from Ibaraki Nature Museum, Vascular Plants collection. 671 records from IG TUT paleontology. 361 records from Tartu University, palaeontology collections. 15403 records from Leiner-Herbar Konstanz. 3912 records from RBINS collections. 178 records from Raw counts of dinoflagellate cysts in several IODP and DSDP holes. 7 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 1 records from Phytoplankton abundance during Mikhail Lomonosov cruise ML47. 5 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV13. 3 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 3 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 786 records from Collection Paleobotanique de l'Universite Paris 6. 43 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 19 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 4 records from (Table 1) Biomass of cysts and active infusoria in the surface layer of the Central Indian Ocean. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 6 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV23. 2 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 2 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 4 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 21 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 43 records from Field Museum of Natural History (Botany) Fungi Collection. 390 records from Inventory of Penessoulou forest (North West Benin). 35 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of ODP Hole 104-643A. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 16 records from (Table S1) Dinoflagellate cysts, pollen and spores of sediment core ABC26. 47 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 78 records from CEPEC-Fungi - Coleção Micológica do CEPEC. 28 records from (Table 6) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-906A. 35 records from (Table 5) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-905A. 10179 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 532 records from Inventory of Bonou and Itchèdè forests in south east of Benin. 15524 records from Universität Salzburg. 1 records from DSMZ Collection of Filamentous Fungi and Yeasts. 4716 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 2175 records from Collection Bernstein - SMF. 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 4 records from Collection Malakologie - SNSD. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 8 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 3761 records from Mountain Invasion Research Network (MIREN) survey. 15 records from Swiss Psyllid (Hemiptera) Collections - Basel. 90 records from Naturhistorisches Museum Mainz, Paleontological Collection. 2 records from MfN - Heteroptera Collection. 2 records from MfN - Auchenorrhyncha Collection. 1 records from MfN - Mallophaga Collection. 18 records from GBIF-D Protozoa data collection. 695282 records from Australian National Herbarium (CANB). 10227 records from Andes to Amazon Biodiversity Program. 5191 records from Botanical Garden Collection. 123 records from WA. 31240 records from ANTARCTIC PLANT DATABASE. 18 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 13310 records from Australian Antarctic Division Herbarium. 9 records from Antarctic Marine Protists species checklist. 1508 records from Royal Museum of Central Africa - Metafro-Infosys - Prelude. 2 records from BCCM/LMG - Laboratory of Microbiology Gent Bacteria Collection. 1 records from Interactive Database of Biodiversity Studies on Terrestrial Arthropod Animals of Korea. 979 records from Korean Ethnobotany Database. 684 records from Factual Database of Native Flora Seeds in Korea. 69 records from Korean Aquatic Vascular Plants. 88124 records from Canadian Museum of Nature Herbarium. 183401 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 460 records from CABI Bioscience Fungus Collection. 1 records from CABI Bioscience Nematode Collection. 78127 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 24085 records from Herbario UNAP. 111515 records from The AAU Herbarium Database. 91215 records from Herbarium (ICEL). 22314 records from Herbarium (AMNH). 290686 records from Observational database of Icelandic plants. 6634 records from Real Jardin Botanico, Madrid: MA-Algae. 25128 records from Real Jardin Botanico, Madrid: MA-Musci. 4071 records from Real Jardin Botanico, Madrid: MA-Hepat. 172 records from Real Jardin Botanico, Madrid: MA-Lichen. 215326 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 135628 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 533675 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 20945 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 14971 records from Herbario de la Universidad de Almeria. 30243 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 39820 records from Jardín Botánico de Córdoba: Herbarium COA. 33944 records from Aranzadi Zientzi Elkartea. 4971 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 4284 records from Universitat de Girona: HGI-Cormophyta. 37044 records from CIBIO, Alicante:ABH-GBIF. 11209 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 36169 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 2967 records from Real Jardin Botanico, Madrid: MA-Funhist. 77 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 19130 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 224703 records from Herbario de la Universidad de Sevilla. 11452 records from Herbario de la Universidad de Sevilla, SEV-Historico. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 56081 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 6050 records from CUBA: Herbario de la Academia de Ciencias, La Habana, Cuba: HAC-Pteridophyta. 1116 records from CUBA:Herbario del Jardín de los Helechos, Centro Oriental de Ecosistemas y Biodiversidad, Santiago de Cuba: BSC-Pteridophyta. 6560 records from CUBA:Herbario del Jardín Botánico Nacional, La Habana, Cuba: HAJB-Pteridophyta. 59580 records from Institut Botanic de Barcelona, BC. 4065 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 1769 records from EPA'S EMAP Database. 1 records from HMAP-History pf Marine Animal Populations (CoML). 1865 records from NODC WOD01 Plankton Database. 30 records from SeamountsOnline (seamount biota) (CoML). 3210 records from HerbarioHerrerense. 7751 records from Natural Geography In Shore Areas (NaGISA) Dataset. 17348 records from Continuous Plankton Recorder database. 1172 records from NBI. 54 records from Bishop Museum Data (OBIS distribution) (USOBIS). 3822 records from Gwaii Haanas Marine Plants (OBIS Canada). 169 records from Bay of Fundy Species List (OBIS Canada). 193354 records from Auckland Museum Botany Collection. 21 records from Database on Forest Disturbances in Europe. 3 records from Grand Manan Basin Benthos (OBIS Canada). 67 records from Scottish Natural Heritage - Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 932 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 11 records from Benthic fauna in the Pechora Sea (EurOBIS). 40 records from MedOBIS (EurOBIS). 173 records from BioMar (EurOBIS). 1 records from Gwaii Haanas Invertebrates (OBIS Canada). 30 records from MarBEF Publication Series data (EurOBIS). 7547 records from Botanic Garden of the Finnish Museum of Natural History. 578 records from AIMS - Bioresources Library (OBIS Australia). 916 records from Posidonia Oceanica Survey 2005 (EurOBIS). 8025 records from Bolus Herbarium Algal Specimen Database (AfrOBIS). 1053 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 5362 records from MICROBIS database. 11 records from Polycystine Radiolarians from the water column and the surface sediments of the World Ocean (OBIS South America, SOUTHERN OCEAN SUB-NODE). 43831 records from Herbarium of Jyväskylä University Museum. 908 records from Plant in Baekdu Mountain (KIDR-PL). 2 records from Naturalis Biodiversity Center (NL) - Coleoptera. 19 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 1343 records from martius-munchen-infocomp. 15846 records from Brassicaceae of Canada. 13570 records from Royal Botanical Gardens Herbarium. 984 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 1657 records from Phragmites of Canada. 5056 records from DAO Herbarium Type Specimens. 8 records from Michigan State University Herbarium Lichens. 192384 records from Bryophytes of Ireland. 79260 records from Paleobiology Database. 191859 records from herbario. 69 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramos "Guantiva -La Rusia", Colombia. 1 records from Lichen Collection of National Museum of Nature and Science. 19628 records from Bryophytes Collection of National Museum of Nature and Science. 12085 records from Algae Collection of National Museum of Nature and Science. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 109497 records from Plant Specimens of Kurashiki Museum of Natural History. 30150 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 14825 records from Herbarium of Kitakyushu Museum of Natural History and Human History. 21794 records from Bryophyte specimens database of Mr. Tsutomu Kodama collection, Osaka museum of Natural History. 2882 records from Individual Sightings. 163650 records from Vascular Plant Collection. 524 records from Arctic Ocean Diversity. 476 records from Biodamaz1. 7284 records from IIAPPoa. 2 records from Arizona State University Lichen Collection. 136059 records from Arizona State University Vascular Plant Herbarium. 24794 records from University of Copenhagen Arboretum. 7939 records from Botany registration database by Danish botanists. 47 records from Nivå Bay species list, Zealand, Denmark. 1 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 12843 records from Herbarium Faeroense. 20568 records from Botanical Museum, Copenhagen. Database of type specimens. 167 records from Priest Pot species list, Cumbria, Britain. 3299 records from Botanical Museum, Denmark. Database of registrations of red listed plants. 128240 records from DAV UC Davis Center for Plant Diversity. 4664 records from Database Schema for UC Davis [TGRC]. 78063 records from California State University, Chico. 115 records from Database Schema for UC Davis [Phaff]. 5592 records from UCD BOTANICAL CONSERVATORY. 41459 records from Herbarium (UNA). 109 records from MEXU/Frutos y Semillas. 31082 records from MEXU/Plantas Vasculares. 8977 records from MEXU/Tipos de plantas vasculares. 40388 records from MEXU/Colección de Briofitas. 5826 records from MEXU/Herbario Los Tuxtlas. 30985 records from MEXU/Asteraceae. 6760 records from Rosaceae and Fabaceae of Kevo region, Northern Finland. 623496 records from NSW herbarium collection. 141961 records from Plants of Papua New Guinea. 315 records from Invertebrate Paleontology Division, Yale Peabody Museum. 26 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 31 records from Invertebrate Zoology Division, Yale Peabody Museum. 1 records from CBS Filamentous Fungi Database. 1 records from DSMZ Bacteria. 1 records from DSMZ Fungi. 6 records from IFO Filamentous Fungi. 1 records from Japan Collection of Microorganisms(Fungi). 2 records from AlgaTerraMovies. 452 records from Algaterra Types. 1004 records from Bridel Herbar. 10606 records from Desmidiaceae Engels. 603 records from Desmidiaceae Mollenhauer. 2134 records from Flora exsiccata Bavarica. 9 records from (Supplement 3) Dinoflagellate cyst count data by species of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 355 records from GEO Biodiversity Day. 199936 records from Herbarium Berolinense. 112508 records from Herbarium Willing. 10 records from Lichen Herbarium Berlin. 1534 records from PonTaurus collection. 27209 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 6 records from Desmidiaceae Rostock. 22790 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 4633756 records from Observations du Conservatoire botanique national du Bassin parisien.. 97293 records from Biologiezentrum Linz. 45767 records from Herbarium Senckenbergianum Görlitz (GLM). 309824 records from United States National Plant Germplasm System Collection. 679717 records from The System-wide Information Network for Genetic Resources (SINGER). 250747 records from Israel Nature and Parks Authority. 54 records from Banc de dades de biodiversitat de Catalunya-MolusCat. 3596 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 121 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 5613 records from The Erysiphales Collection at the Botanische Staatssammlung München. 1470 records from The Erysiphales Collection at the University Halle-Wittenberg. 24 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 423 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 51 records from Sea Algae. 184 records from Green Algae. 1377 records from IndOBIS, Indian Ocean Node of OBIS. 531 records from Biological Collection, National Institute of Oceanography, Goa, India. 9081 records from Cameroon National Herbarium. 3 records from TSB Lichen Herbarium. 704 records from DSMZ Collection on Plant Cell Cultures. 37516 records from Nordic Genetic Resources. 22817 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 95982 records from USU-UTC Specimen Database. 6826 records from AWI-Herbarium Marine Macroalgae. 287 records from invertebratezoology. 1 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 9743 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 2631 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 15658 records from Institut Botanic de Barcelona, BC-Histórico. 21380 records from Bryophyte collection. 34481 records from Herbarium de Geo. B. Hinton, México. 1945 records from HBGBryophyta - Herbarium Hamburgense. 19890 records from HBGSpermatophyta - Herbarium Hamburgense. 17498 records from Impetus - Herbarium Hamburgense. 42 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 268 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Juergen Homeier. 420 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 2500 records from Visual Plants (144.41.33.158) - Herbarium specimen from the Estacion Scientifica San Francisco, Southern Ecuador. 405 records from Visual Plants (144.41.33.158) - Private collection of Rainer Bussmann. 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 38 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Florian Werner. 30 records from Visual Plants (144.41.33.158) - Private collection of Manfred Kueppers. 27 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Baerbel Bleher. 73 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ben Hell. 126 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ulf Soltau. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 17 records from Visual Plants (144.41.33.158) - Private collection of Vindas Jorge, Costa Rica. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 83 records from Visual Plants (144.41.33.158) - Private collection of Juergen Homeier. 38 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Helmut Dalitz. 60 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Steffen Matezki. 63 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 3 records from Visual Plants (144.41.33.158) - Private collection of Barbara Kueppers. 20 records from Visual Plants (144.41.33.158) - Private collection of Helmut Dalitz. 4 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Frank Haubrich. 50 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 9 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Daniel Piechowski. 3 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Frederike Proewe. 30974 records from Joint Nature Conservation Committee - Vegetation surveys of coastal shingle in Great Britain. 133 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 545 records from CeDoc de Biodiversitat Vegetal: BCN-Phycophyta. 78 records from Electron Micrograph Database - Marine Specimens. 182 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 4616904 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 2586 records from Plant Specimens of Lake Biwa Museum. 15879 records from Angiosperm specimens of Iwate Prefectural Museum. 36991 records from Vascular Plants Collection of Sagamihara City Museum. 7127 records from MEXU/Asclepiadaceae. 437908 records from Harvard University Herbaria. 30917 records from Vascular plants of south-central China. 82585 records from Specimen Database of Colorado Vascular Plants. 192 records from Visual Plants (144.41.33.158) - Private collection of Eberhard Fischer. 232 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Helmut Dalitz. 1235 records from Visual Plants (144.41.33.158) - Herbarium specimen from "EA", Kenya. 832 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 504 records from Visual Plants (144.41.33.158) - Herbarium specimen from "USJ", Costa Rica. 137 records from Visual Plants (144.41.33.158) - Herbarium specimen from "BIEL", Germany. 124897 records from BioGIS - Vascular plants - A. Danin's grid database. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 4 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Annette Wolter. 17218 records from Herbarium BSG Vascular Plants. 70365 records from inatura - Erlebnis Naturschau Dornbirn. 679 records from Inventaire National du Patrimoine Naturel : Programme national espèces végétales de la Directive Habitat. 11622 records from French Grapevine Genetic Resources Center. 489 records from Galapagos grasses and sedges. 4124 records from Herbario de la Universidad de La Laguna:TFC-Bry. 1 records from ORN. 67 records from Herpetology. 961603 records from EURISCO, The European Genetic Resources Search Catalogue. 309 records from Central Scotland Forest Trust - South Lanarkshire peatland records 2013. 78 records from Electron Micrograph Database (Australian Antarctic Data Centre). 5058 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 20 records from NCOS1959_Crustacea (OBIS China). 108 records from NCOS1959_Mollusca (OBIS China). 17 records from Database of invertebrates collected in Mongolia. 88496 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 15537 records from CVRD - Herbário da Reserva Natural Vale. 4 records from Aves MZS. 1000 records from Plant Specimens of Taga Town Museum, Shiga Pref., Japan. 126077 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 30625 records from Kochi Prefectural Makino Botanical Garden. 1612 records from Plant Specimens of Wakayama Prefectural Museum of Natural History. 3651 records from Plant (MNHM-PL). 18192 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 10635 records from Bryophyta Specimens of The Nagoya University Museum. 1109 records from MEXU/Colección Histórica. 6834 records from MAR - Herbário do Maranhão. 70 records from MAL. 21 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 1267 records from DNA and Tissue Bank of the Natural History Museum of Denmark. 106732 records from USGS South Florida Fish and Invertebrate Assessment Network Braun Blanquet. 915 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 2905 records from UAM Herbarium (ALA), Algae Collection (Arctos). 177494 records from Primer censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 256069 records from Staffordshire Ecological Record - SER Site-based Surveys. 93623 records from Biodiversitätsdatenbank des Landes Salzburg. 944 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (siembra). 2399 records from Herbarium BSG Bryophyta. 60 records from Naturalis Biodiversity Center (NL) - Aves. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 33 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 508 records from Guyane_Cacaoyer. 2 records from University of Alberta Museum of Zoology Amphibian and Reptile Collection (UAMZ). 2255 records from Plant Systematics Laboratory, Ajou University, Korea. 425 records from Moss sampling in the Windmill Islands and the Vestfold Hills. 24438 records from Herbario de la Universidad de Arizona, EUA. 84555 records from Repatriación de datos del Herbario de Arizona (ARIZ). 4044 records from Cactáceas Columnares de México (IE-MORELIA, UNAM). 1 records from Colección de Entomopatógenos de México (CNRCB). 82953 records from Vascular Plants, Observations, Oslo (O). 9167 records from Árboles y Arbustos Nativos para la Restauración Ecológica y Reforestación de México (IE-DF,UNAM). 1428 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 9031 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 5566 records from Colecciones de George Boole Hinton depositadas en el herbario de Kew: Familia Leguminosae. 59543 records from Programa de repatriación de datos de ejemplares mexicanos. 49889 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 752 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1604 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 3329 records from Universitat de València, Colecciones de Criptógamas: VAL_Briof. 2 records from Christopher Walker collection of Glomeromycotan fungi. 32 records from UCM Amphibian and Reptile Collection (Arctos). 231001 records from Oklahoma Vascular Plants Database Provider. 74018 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 316 records from Moss species from Heard Island, 1987 and 2000. 3 records from (Table 2c) Percentages of energy flow of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 482 records from BÜG. 357 records from LaBoOb02. 18 records from Pfrimmersbachtal. 88 records from Klutensee. 69 records from Überall ist Wunderland. 156 records from DJH. 122 records from Am Moosangerweg. 69 records from Frau Voss. 367 records from Danielsberg (Mölltal, Kärnten). 24 records from Streuobstwiese RSG (Cham). 309 records from Naturschutzgebiet Sistig-Krekeler-Heide. 134 records from AKG-Gelände (Bensheim). 196 records from FFH-Gebiet Ahrbachtal. 73 records from Botanischer Garten (Saarbrücken). 88 records from Trockenhang Greinhartsberg Edelfingen. 742 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 90 records from Hamberger Brücke / Würmtal (Pforzheim). 72 records from Artenvielfalt auf den Elbwiesen (Dessau). 18 records from Schulgelände (Wetter). 427 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 49 records from Sandhofen. 164 records from Kernberge und Umgebung (Jena). 191 records from Schlichemquelle (Tieringen/Meßstetten). 186 records from Mooswald (Freiburg). 549 records from Gemeinde Sursee. 173 records from Gewann Krampf (Heilbronn). 12 records from Angelberger Forst - Klassen 3 a und 3 b. 318 records from Naturschutzstation Schmidsfelden. 172 records from Landschaftspflegehof (Berlin). 454 records from Naturschutzgebiet Bausenberg. 182 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 12 records from Altholzparzelle Eilenriede Hannover. 53 records from Schulhof Bühlschule Giengen. 525 records from Schlern - (Bozen). 817 records from GEO Hauptveranstaltung Tirol (Innsbruck). 61 records from Schulgelände IGS Kaufungen. 165 records from Schule Sulzbach (Oberegg). 270 records from Zukünftiges NSG Höftland/Bockholmwik. 95 records from Artenbestimmung. 543 records from Königstetten. 109 records from Frauenholz (Holzmaden). 327 records from Freiburger Tag der Artenvielfalt. 63 records from Erzental (Oberotterbach). 173 records from Langes Tannen (Uetersen). 228 records from Gelände des IVL (Zeckern). 141 records from Stausee (Oberdigisheim/Meßstetten). 111 records from Naturschutzgebiet Bausenberg (Niederzissen). 438 records from Erlengraben/Lipp-Tal (Östringen). 145 records from Wald und Wiese am Buchwald. 204 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 259 records from NSG Karwendel. 176 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 407 records from Neckartalsüdhang (Horb). 169 records from Umgebung der Gesamtschule Hamburg-Winterhude. 88 records from Langes Tannen. 56 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 92 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 98 records from Schulgarten Huttenheim (Philippsburg/Baden). 151 records from Sonnentaugemeinschaft. 75 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 28 records from Artenvielfalt der Nordsee - Helgoland. 157 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 187 records from Philosophenwald und Wieseckaue in Gießen. 34 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 58 records from Artenvielfalt auf Restbauernhof. 64 records from Wiese und Weide am Waldrand von Gusterath. 73 records from Blumenrather Heide / Virneburg. 262 records from Cuxhavener Küstenheiden. 42 records from Umgebung von Schorndorf. 717 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 76 records from Danisco-Wiese. 295 records from nazza. 21 records from Birkenpilz. 167 records from katzenbuckel. 176 records from Promberg1. 300 records from Biologische Station im Kreis Wesel. 344 records from GEO-Hauptveranstaltung (Insel Vilm). 578 records from GEO-Hauptveranstaltung (Duisburg). 85 records from Wanderweg am Windebyer Noor (bei Eckernförde). 476 records from BUND - Dassower See (Lübeck/Dassow). 279 records from Wildes Bremer Leben im Park. 99 records from Entdeckertour am Muldestausee. 164 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 75 records from Unser Schulgelände. 394 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 112 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 20 records from Nottekanal, Klasse 7 - 10. 76 records from Luch Niederlehme, Schüler der Klasse 7. 21 records from Stadtbiotop Ulrichteich. 279 records from Pilstingermoos. 226 records from Artenfülle um das Schalkenmehrener Maar. 112 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 185 records from Riedensee. 70 records from Streuobstwiese Kattenhund (Schleswig). 264 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 314 records from Gurgltal (Tarrenz). 16 records from Absolute abundances of organic-walled dinoflagellate cysts from 116 marine surface samples. 36 records from Überschwemmungsgebiet der Wied. 369 records from 20 Jahre Naturschutzgebiet Dreienberg. 31 records from Hüttenseepark (Meißendorf). 27 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 78 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 152 records from Heinersdorfer Sumpfwiese. 1 records from Schaalbach. 98 records from 4. GEO-Tag in Eberbach. 35 records from Deutsche Schule Budapest. 206 records from schulgarten. 33 records from GEO-Hauptveranstaltung Bodden (Vilm). 85 records from NSG Nollig. 159 records from Pottundkopp. 176 records from Knechtweide (Kohlfurth). 2 records from uno city. 5 records from Landesgartenschau. 150 records from Wildkräuter. 40 records from Schulumgebung Grüterschule, Rheine. 171 records from Wald am Schloss Wittgenstein Bad Laasphe. 81 records from Industriegebiet (Kempen). 67 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 133 records from Ökostation (Freiburg). 86 records from Bergbaufolgelandschaft am Muldestausee. 115 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 72 records from Regionalpark(Hattersheim). 32 records from Langes Tannen in Uetersen. 83 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 75 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 163 records from Schulhof Gymnasium Hürth Bonnstrasse. 49 records from Schulhof Goethe-Gymnasium (Emmendingen). 227 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 140 records from Kiesbagger (Mittelhausen). 55 records from Biotop Binsenwiesen (Wehrheim/Taunus). 101 records from NSG Berschau - Auengebiet (Neustadt / Wied). 51 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 38 records from Schulumfeld Albert-Einstein-Gymnasium (Sankt Augustin). 311 records from Gemeindegebiet Weikendorf (Marchfeld). 150 records from Umgebung der Gesamtschule Winterhude (Hamburg). 161 records from Lebensraum Gesamtschule (Langerwehe). 44 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 68 records from Tiergarten (Zeitz). 63 records from Natur aus zweiter Hand am Muldestausee. 68 records from Schulgelände Schule auf der Aue, Münster. 85 records from "Tre Pini" (Montebelluna, Italien). 49 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 201 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 163 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 56 records from Schloß Türnich (Kerpen). 128 records from Unser Schulhof - eine Apotheke. 106871 records from Field Museum of Natural History (Botany) Bryophyte Collection. 148 records from Quarrendorfer Landschaftsschutzgebiet. 146 records from Faberpark (Nürnberg/Stein). 23 records from Unser Schulhof. 75 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 209 records from Streuobstwiese Kugelberg (Ulm). 108 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 135 records from Wiese am Waldrand (Gurtweil). 47 records from Südwestlich der Parkwiesen. 62 records from Wismar Bucht coast-watching. 104 records from Urwald 1 (Bad Waldsee). 55 records from Schulprojekt (Bremen). 191 records from Fuldaaue (Stadtgebiet Fulda). 255 records from Stadtgebiet (Dannenberg). 74 records from Muehlenbach bei Friesheim. 223 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 131 records from Renaturierung Werse (Innenbereich Beckum). 66 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 499 records from Bergkamen- Bergehalde Großes Holz. 7 records from Boraginaceae (Cynoglossum cherangauiense). 33 records from Lüner Holz (Lüneburg). 129 records from Stadt Königs Wusterhausen. 128 records from Stadtpark Sulzbach-Rosenberg. 138 records from Lindau im Bodensee. 105 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 41 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 125 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 75 records from Schulhof und Anlagensee in Nellingen. 132 records from Tiergarten Straubing. 60 records from Vorderer Tiergarten (Dessau). 101 records from Bizzenbachtal (Wehrheim/Taunus). 134 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 137 records from Werremündung im Schwarzatal. 25 records from Klimaoasen in Köln. 159 records from Schlattstaller Tal (Lenningen). 92 records from Naturschutzgebiet Müchelholz (Mücheln). 1817 records from Eppingen und Umgebung. 93 records from Steinbruch Haas Stuttgart-Münster. 47 records from Küste Wismar-Wendorf bis Hoben. 28 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 18 records from Hemmerder Schelk (Unna). 438 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 56 records from Weidenhüttendorf an der Würm (München). 204 records from renaturierter Main (Kemmern bei Bamberg). 52 records from Unterbrucker Weiher. 161 records from 3. Tag der Artenvielfalt Hockenheim. 101 records from Prophetensee Quickborn. 96 records from Halberg bei Neumorschen. 60 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 63 records from Hintere Halde. 52 records from Steinbruch Pluwig. 87 records from Lebensraum Stadt und Park. 112 records from Schussenaue (Weingarten). 187 records from Wupperaue bei Kemna (Wuppertal). 639 records from CRSN-Lwiro Herbarium, Kahuzi-Biega National Park (CABIN project). 113 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 12 records from An der Ohm, (Wettsaasen). 28 records from Freiheitsring (Frechen). 25 records from Schulgarten Paul-Schneider-Schule, Münster. 28 records from Artenvielfalt der Nordsee - Sylt. 9 records from Spandau HBO. 71 records from Dreilinden Gymnasium-Schulgelände. 36 records from Maschwiesen Laatzen. 97 records from Himmelmoor. 135 records from Altenburg bei Bamberg. 255 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 67 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 142 records from Naturerlebnisraum Koppelsberg. 158 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 317 records from Walldorf-Wiesloch: "Natur über den Gleisen". 201 records from Innenstadt Göttingen - Natur Zuhause. 141 records from Mißmahlsche Anlage. 42 records from Teich Berlin Wuhlheide. 46 records from Ruhrwiesen bei Neheim-Hüsten. 58 records from Schulgelände Städtisches Gymnasium. 17 records from Artenvielfalt im Umfeld der Burgwegschule. 178 records from Naturgarten Langenholtensen. 104 records from VSN-Wiese. 95 records from Arteninventar rund um den Rannahof. 244 records from Tag der Artenvielfalt. 70 records from Artenvielfalt auf dem Schulgelände. 292 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 39 records from Schulgelände SGD/Viersen. 314 records from Unna-Mühlhausen, Wiesen. 717 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 4 records from Dinoflagellate cyst abundances at DSDP Site 94-607 from the North Atlantic (Appendix B). 42 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 1015 records from Caracterización vegetal y rasgos funcionales de plantas colectadas en un gradiente altitudinal de bosque altoandino a páramo en el Santuario de Fauna y Flora Iguaque. 1 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB04 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 2 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 6 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 423 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 2 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 1 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1992. 1 records from Microplankton abundance in the euphotic zone of the Aegean and Levantine Seas in Sepmember-October 1987. 78 records from (Table 1) Count data of organic-walled dinoflagellate cysts in surface sediment samples from the Benguela System. 126083 records from USF Herbarium. 23801 records from Swan Coastal Plain Survey. 267861 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 42 records from Results of palynological analysis of Hole 302-M0004A. 3258 records from HPAN - Herbário do Pantanal "Vali Joana Pott". 1 records from Foraminifera abundance of Hole 39-357. 4984 records from Herbier Ecole de Faune. 4 records from Foraminifera abundance of Hole 17-171. 2056 records from Spring bryophyte flora of Salpausselkä (Ulvinen 1955 & Juutinen 2006). 1 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 150 records from Vegetatively propagated Allium collection. 37 records from (Appendix A) Dinoflagellate counts in surface sediments of cores taken in the North Pacific. 61 records from Lichens of North-Eastern Poland. 2034 records from Herbarium of Namur. 300 records from National Botanic Garden Belgium - Martius. 2 records from Foraminifera abundance of Hole 61-462. 66210 records from Natural History Museum, University of Tartu. 5 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 105558 records from University of British Columbia Herbarium (UBC) - Algae Collection. 4021 records from Herbarium Specimen of the Institute of Traditional Medicine, Tanzania. 63230 records from Herbarium of Umeå University (UME). 58 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 208658 records from Mosses (S). 3 records from Amphibian observations from Nida Valley. 243 records from Caracterización de coberturas vegetales en el páramo de Rabanal. 182770 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 513351 records from Field Museum of Natural History (Botany) Seed Plant Collection. 90 records from Herbario MAIA, colección de Ericas del INIA-CIFOR. 50118 records from MBML-Herbario - Herbário Mello Leitão. 3278 records from Espèces vasculaires endémiques et orchidées (CITES). 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 564 records from Central Scotland Forest Trust - Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 22 records from British Lichen Society - BLS Lichen Database: England. 203 records from Natural England - Invertebrate Site Register - England.. 2107 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 2 records from Benthic foraminifera abundance of Hole 84-567A. 1 records from Benthic foraminifera abundance of Hole 84-569. 1 records from Benthic foraminifera abundance of Hole 84-569A. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Benthic foraminifera abundance of Hole 84-569, Part 1. 12 records from Range table from benthic foraminifers in ODP Hole 143-865A. 21 records from Range table from benthic foraminifers in ODP Hole 143-866A. 2 records from Range table from benthic foraminifers in ODP Hole 144-879A. 14 records from Weevils of Wales and England. 25819 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 304 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 10 records from Range table from benthic foraminifers in ODP Hole 171-1049A. 1 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 1 records from Range table from benthic foraminifers in ODP Hole 171-1051A. 2 records from Range table from benthic foraminifers in ODP Hole 171-1052E. 59905 records from Polish gene bank – passport data of plants accessions which are important in human life. 1 records from Dinoflagellate abundance of Hole 81-552. 2 records from Dinoflagellate abundance of Hole 81-553A. 7 records from Dinoflagellate abundance of Hole 81-555. 1 records from Dinoflagellate abundance of Hole 81-552. 3 records from Dinoflagellate abundance of Hole 81-552A. 2 records from Dinoflagellate abundance of Hole 81-553A. 3 records from Dinoflagellate abundance of Hole 81-554. 1 records from Dinoflagellate abundance of Hole 81-554A. 20 records from Dinoflagellate abundance of Hole 81-555. 5 records from Dinoflagellate abundance of Hole 14-144. 1 records from Dinoflagellate abundance of Hole 22-214. 5 records from Dinoflagellate abundance of Hole 28-270. 1 records from Dinoflagellate abundance of Hole 28-274. 27 records from Dinoflagellate abundance of Hole 94-607. 4 records from Dinoflagellate abundance of Hole 94-607A. 11 records from Dinoflagellate abundance of Hole 94-611. 28 records from Dinoflagellate abundance of Hole 94-611C. 9 records from Dinoflagellate abundance of Hole 40-365. 1 records from Pollen and spore abundance of Hole 42-379A. 8 records from Pollen and spore abundance of Hole 42-380. 7 records from Pollen and spore abundance of Hole 42-380A. 1 records from Pollen and spore abundance of Hole 42-381. 14 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-898A. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-900A. 2 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-907A. 19 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-911A. 12 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 1 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1168A. 4 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1169A. 2 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1170A. 1 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171A. 23 records from Results of palynological analysis of Hole 302-M0002A. 4 records from Results of palynological analysis of Hole 302-M0004B. 1031575 records from Belgian IFBL Flora Checklists (1939-1971). 46 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 68 records from Marine palynomorph abundance estimates of sediment core CRP-2A (Fig. 2). 1561805 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 2 records from Avistamientos de Biodiversidad Marina / Marine Biodiversity Sightings. 649 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 172 records from EEIKO Base de datos sobre plantas invasoras. 38 records from Greater Manchester Ecology Unit - Distribution of Species of Conservation Interest in Greater Manchester. 15 records from (Table 2) Calcareous nannofossil abundance in ODP Hole 164-994C sediments. 51 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 1177 records from Spécimens d'herbiers de G. Fenoul (FEN). 2 records from Middle Miocene microflora of Zidlochovice (Czech Republic). 148614 records from New Mexico Biodiversity Collections Consortium database. 983 records from Perchtoldsdorfer Heide. 141 records from Naturpark Drömling. 241 records from Schwanheimer Wald. 260 records from Freiburger Netzwerk Artenvielfalt. 155 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 47 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 156 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 147 records from Berkel. 35 records from Tag der Artenvielfalt mit SchülerInnen des Europa-Gymnasiums in Wörth am Rhein. 51 records from Tag der Artenvielfalt mit SchülerInnen des Leibniz-Gymnasiums in Neustadt a.d.W.. 30 records from NSG Dellwiger Wald, Dortmund. 355 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 123 records from NSG Haunestausee, Hauneteiche. 48 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 29 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 27 records from Biosphärenreservat Münsinger Alb. 31 records from Töpinger Mischwald. 24 records from Phragma-Thermis/Thessaloniki. 38 records from Flora und Fauna in unserer Kita. 13 records from Klosterwald Itzehoe. 12 records from Waldstück am Schullandheim Bad Bederkesa. 8 records from Auenwiesen und Trockenrasen. 57350 records from Colorado State University Herbarium. 24201 records from EKY_Darwincore. 55685 records from MISS_DC_01MAR2006. 521 records from FernsDarwinCore. 8974 records from NCSU_Darwincore. 3831 records from Sponges of Rathlin Island. 230194 records from UA Herbarium. 388 records from Lustadter Wald .. 64 records from Waldwandel in Monschau-Mützenich-Boverei. 56 records from Gymnicher Mühle. 165 records from Kohlstattbrunnental. 87 records from Naturnahes Tal in Siena. 258445 records from R. L. McGregor Herbarium Vascular Plants Collection. 61 records from Departamento de Investigación y Experiencias Forestales de Valonsadero de la Junta de Castilla y León: JCYL-Fungi. 10920 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1796 records from EDIT - ATBI in Gemer area (Slovakia). 90 records from ELM paleontology. 1092189 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 8276 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 6536 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 1 records from Vertebrate specimens of Jyväskylä University Museum. 187800 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 38917 records from Gunma Museum of Natural History, Vascular Plant Specimen. 38020 records from Vascular plants collection of Hiratsuka City Museum. 35489 records from MEXU/Colección de Plantas Acuáticas. 521 records from Artenvielfalt am Schlern. 489 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 140 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 172 records from VFD-BW, Dinkelberg: Pferdeweiden Oberminseln. 158 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 151 records from VFD-BW, Schwäbische Alb: Pferdeweiden Zainingen. 121 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 98 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 607514 records from Plant. 14411 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 2325 records from Jardín Botánico Atlántico, Gijón: JBAG. 145153 records from DUKE Bryophyte Collection. 78926 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 3772 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 622091 records from Biological and palaeontological collection and observation data MNHNL. 20972 records from Sukkulentensammlung Zürich. 148 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 108105 records from Botany Division, Yale Peabody Museum. 1 records from Entomology Division, Yale Peabody Museum. 3 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 80772 records from Paleobotany Division, Yale Peabody Museum. 4 records from Vertebrate Paleontology Division, Yale Peabody Museum. 382 records from Tag der Artenvielfalt im Taubental. 64 records from VFD-RP, Taunus: Bergweide Dehe. 5 records from BIOLOGICAL SCIENCES DATA. 42 records from KU Museum of Invertebrate Paleontology. 291 records from Collection Pisces SMF. 5934 records from HUTO - Herbário da Universidade de Tocantins. 7 records from Collection Mollusca SMF. 34 records from Collection Echinodermata fossil SMF. 2 records from Collection Polychaeta SMF. 62 records from Collection Mikropaläobotanik SMB. 85165 records from Herbarium Senckenbergianum (FR). 185 records from Collection Aves (bird skeletons) SMF. 1580 records from Collection Paläobotanik SMB. 7 records from Collection Bryozoa SMF. 138 records from Collection Cnidaria fossil SMF. 2367 records from Collection Messelpaläobotanik SMB. 3 records from Collection Tunicata SMF. 1 records from Collection Tardigrada SMF. 267634 records from SINGER Coordinator. 3538 records from NHT_flora. 297 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 36 records from Type Localities for organisms and fossils first described from Antarctica. 11955 records from MEXU/Leguminosae. 2618 records from MEXU/Agavaceae. 3438 records from MEXU/Flora de Oaxaca. 1 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Invertebrate Observation Records other than Lepidoptera. Pre-2010 for Cumbria. 989 records from MEXU/Pinaceae. 894 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Algae. 34955 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 11098 records from Herbario de Universidad de Murcia: MUB. 48 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 1 records from Joseph F. Rock Herbarium. 1261 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 84834 records from Database of Native Plants in Taiwan. 124950 records from National Inventory of Swiss bryophytes. 51476 records from Bryophyte Collection - University of Washington Herbarium (WTU). 505 records from Mycological Collection - University of Washington Herbarium (WTU). 268 records from Lichen Collection - University of Washington Herbarium (WTU). 2199 records from Plantlife International - Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 5 records from Benthic macrofauna abundance and biomass in surface sediment during cruise CD86. 2 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG93. 12 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG95A. 5 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 184 records from Herbier de la Guyane. 84516 records from University of Ghana - Ghana Herbarium. 36885 records from Seaweeds of Ireland. 1958 records from Plant of Folklore (KIDR-PL). 599 records from NHT flora. 273 records from E39 Lyngdal - Ålgård. 1 records from Fossil (SMNH-FO). 6659 records from Scottish Environment Protection Agency - River macroinvertebrate data for 2005 and 2006. 161650 records from Herbarium of Taiwan Forestry Research Institute. 1423 records from Inventaire National du Patrimoine Naturel : CBN du Massif Central. 191 records from Herbarium specimens of Bamboo collection Prafrance Générargue (BAMBO). 2 records from Insect Arthropods (KIDR-IN). 23541 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 1942 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Pereira, Risaralda. 2508 records from UAM Earth Sciences Collection (Arctos). 140 records from Plant Living in Water (KIDR-PL). 1 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 73645 records from Herbario Amazónico Colombiano. 677 records from Plants from India in the vascular plant herbarium, Natural History Museum at the University of Oslo (NHM-UiO). 33274 records from West African Vegetation Database. 7513 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 1368 records from Plant - Seed (KIDR-PL). 1137 records from Plantas Acuáticas de la Orinoquía Colombiana. 736 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 489632 records from Precis Plant Data. 7971 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 2 records from Carpatica Operation. 4591 records from WII Herbarium Dataset. 318 records from Fossil (WSHN-FO). 195759 records from National vegetation diversity inventory and mapping plan. 86834 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 4201 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 2451 records from Algae (NSMK-AG). 2 records from The reptiles, amphibians and fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 22113 records from West-, Central- and East African Plants Databases. 9 records from British Lichen Society - BLS Lichen Database: Wales. 30358 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 161 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 5621 records from Vascular Herbarium, NMBU. 119 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Black Poplar survey. 4508 records from Contribution à la gestion durable des forêts : Caractéristiques écologiques et structurales de la forêt naturelle d’Akpè (Lama) au Sud du Bénin.. 763 records from Briòfits d'Andorra. 505437 records from Wetland Inventory (NV). 18597 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 32 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 28801 records from The DNA and Sample Repository at AIT. 176 records from Jardín Botánico Uniamazonia JBUA. 2649 records from KTU Pteridophyta. 1703416 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 3 records from Naturalis Biodiversity Center (NL) - Porifera. 251 records from Powys Flora Conservation - Welsh Orchid Survey 2009. 985 records from National Trust - Sutton Hoo species data held by The National Trust.. 77120 records from UPCB - Herbário do Departamento de Botânica. 1781 records from Soft Wheat French National Collection. 300 records from National Botanic Garden Belgium - Martius. 11024 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 443 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 1458 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 3486 records from Faun. 8099 records from tef-database. 68 records from (Table T1) Neogene dynoflagellate cyst occurrence in ODP Hole 186-1151A sediments. 44 records from Parcela Permanente en el Pantano Martos. 3078 records from condoncollection. 194 records from Queensland Museum provider for OZCAM. 42 records from Hertfordshire Biological Records Centre - HBRC Wildlife Site Surveys, Hertfordshire. 7 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in Quaternary sediments from ODP Hole 189-1172A. 4283 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 424 records from Taxonomic Revision of the Ant-Acacias (Fabaceae, Mimosoideae, Acacia, Series Gummiferae) of the New World. 622 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Himalayan Balsam Survey. 887 records from ARKO gamle edellauvtrær. 686 records from Heritage Trees of Ireland. 60197 records from Flora d'Andorra. 2 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 11805 records from HURB - Herbário do Recôncavo da Bahia. 95 records from CUMV Amphibian Collection (Arctos). 9810 records from National System of Protected Areas in Poland - Plants. 1457 records from Plant (JNHM-PL). 543000 records from Aarhus University Palm Transect Database. 5953 records from Elaboration du tarif de cubage multispécifique. 1465 records from University of Amsterdam (NL) - Páramo vegetation research, Santa Marta and Perijá, Colombia. 15702 records from ArtenFinder. 2 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1171D sediments. 607 records from Inventory of Bassila forest (North-Benin). 704287 records from Lund Botanical Museum (LD). 23328 records from kpabg_hepatics. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 7380 records from The Vascular Plant Collection at the Herbarium Tubingense. 311 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 499 records from Plant (KOBG_PL). 8 records from A new species of Orthosiphon (Lamiaceae) from Angola. 5 records from EcoRecord - Bird records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 3387 records from National Trust - Ickworth species data held by The National Trust.. 746339 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 4722 records from HVAT - Herbário do Vale do Taquari. 112 records from iHerbarium. 2452 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejo de Páramos Frontino-Urrao y Citará. 1280217 records from Geographically tagged INSDC sequences. 24124 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 12 records from Collembola Collection. 17166 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 96 records from Guadeloupe_manguier. 1468 records from Fieldjournal.org observation database. 2 records from Field Museum of Natural History (Botany) Lichen Collection. 6394 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 2195 records from Quadrige. 13996 records from TEPB - Herbário Graziela Barroso. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 36657 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 6200 records from HTSA - Herbário do Trópico Semiárido. 288 records from Plant (SMNH-PL). 7971 records from Herbarium togoense. 10179 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 1294 records from Open Mosaic Habitat Survey Group - Plants recorded during Open Mosaic Habitat survey in England and Wales (2012). 934 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Japanese Knotweed Survey. 49 records from Aphidoidea Collection. 1207416 records from Norwegian Species Observation Service. 23047 records from HVASF - Herbário Vale do São Francisco. 1102 records from Plantas laguna El Tinije. 39278 records from Irish vascular plant data 1999-2009. 20135 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 25 records from William Nylander lichen collection. 87309 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 31 records from Herbier Husnot, Hepatica Galliae. 2116 records from SANBI: Rare and Threatened Plants (Cape Floristic Region, 1864-2008). 21299 records from HST - Herbário Sérgio Tavares. 2666 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Perijá. 336 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (verified). 8158 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 24970 records from Colección de Herbario. 271 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 541 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 7416 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 25 records from Dinoflagellate cysts from the Upper Hauterivian (Cretaceous) of a claystone-marlstone succession in the clay-pit Frielingen. 116772 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 11 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6331 records from R-Tipos - Herbário do Museu Nacional - Tipos. 221 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 5360482 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 968 records from Herbier_CNSF. 50 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 2784 records from Kauai Invasive Species Committee - Pest Surveys - 2001-2011. 320 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 1867 records from Rocky Shore Macroalgae. 1079 records from Wildlife Sightings. 1 records from Herbier Louis-Marie (QFA) - Collection de lichens. 926 records from John Muir Trust - Knoydart Bryophytes, 1990. 8389 records from SBT-Living. 678 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 836 records from SJRP-Algae - Herbário de algas de São José do Rio Preto. 411223 records from Bernice P. Bishop Museum. 5354 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 67 records from CUMV Reptile Collection (Arctos). 49222 records from FURB - Herbário Dr. Roberto Miguel Klein. 1837 records from Fremmede arter - spredningsvegen «import av planteprodukter». 1277 records from Mongolian Plant (MMNH-PL). 1668 records from Helechos de la jurisdicción de Corantioquia. 6729 records from National Invasive Species Database. 2 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from Lichens of Knyszyn Forest. 64 records from Raw counts of dinoflagellate cysts of sediment core DP30PC. 19253 records from Irish Crop Wild Relative Database. 301768 records from Carnet en Ligne. 22621 records from Botanical Society of the British Isles - SNH Site Condition Monitoring - Vascular plants (2000-2006). 8918 records from CRI - Herbário Pe. Dr. Raulino Reitz. 115 records from SuLaMa plant monitoring. 4632 records from HUEG - Herbário da Universidade Estadual de Goiás. 364481 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 21443 records from Staffordshire Ecological Record - SER Species-based Surveys. 192 records from Herbario IES San Isidoro de Sevilla. 17245 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 118314 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 23 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 111 records from Mollusca Collection. 10381 records from Seed collection – Dead seeds for evaluation and observation purposes. 4150 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 1 records from UTEP Vertebrates. 23 records from ECatSym: Electronic World Catalog of Symphyta. 7639 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 6768 records from Composición florística y estructura de dos parcelas permanentes en bosques secos tropicales del municipio de Mendéz, Tolima. 13903 records from Tullie House Museum - Tullie House Museum. Cumbria Wildlife Trust survey records from 1970 - 2007 of Cumbria Wildlife Sites. Various.. 175119 records from The Flora of County Wexford. 5674 records from Condon Fossil Collection. 34 records from Levantamento de Herbáceas da RDS Uatumã. 27059 records from Colección del Herbario PSO de la Universidad de Nariño. 18 records from CU Invertebrate Paleontology. 18052 records from UFACPZ - Herbário da Universidade Federal do Acre. 718857 records from Royal Botanic Garden Edinburgh Herbarium (E). 9377 records from tan-database. 3704 records from All observations extracted from the Flora of Northumberland and Durham 1831. 2357 records from Herbarium J Räsänen. 3992 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 64723 records from Michigan State University Herbarium Vascular Plants. 1429 records from Herbier du Muséum Henri-Lecoq de Clermont-Ferrand - Rosacées. 5 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2002. 39260 records from Flora of County Cavan. 332 records from Forster herbarium, Göttingen (GOET). 326739 records from Botany (UPS). 1823 records from European Molecular Biology Laboratory Australian Mirror. 395512 records from Instituto de Ciencias Naturales. 329 records from Microbial Culture Collection, National Institute for Environmental Studies. 354 records from Fossil (GNHM-FO). 1164 records from Seil Natural History Group - SNHG Biological Records Dataset. 2994 records from Museu de Ciències Naturals de Barcelona: BGJBB. 3685 records from CNMT - Herbário Centro Norte Mato Grossense. 10375 records from Type herbarium, Göttingen (GOET). 1 records from Collection botanique Letendre (abbé) (BOUM). 333153 records from National Forest Inventory (SLU). 93601 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 617 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 18959 records from Herbarium Specimens of Bonin and Ryukyu Islands. 17 records from Levantamento de Herbáceas do PARNA Jaú. 1 records from bugland. 25378 records from HAS - Herbário Alarich Rudolf Holger Schultz. 908 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 9614 records from University of British Columbia Botanical Garden Collections (UBCBG). 3079 records from SMNS Palaeontological collection - Fossil plants. 9719 records from The Orchid Atlas of Western Australia. 442 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 4663 records from Estonian Nature Observations Database. 1031 records from Geneva Herbarium – Boissier's Flora Orientalis (G-BOIS). 5 records from Inventaire National du Patrimoine Naturel : Insectes Coléoptères Saproxylophages de France. 3664 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 10907 records from Census of species recorded during phytosociological surveys in Benin. 1609 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Pinus sylvestris pioneer forest. 6774 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia. 1 records from Cnidaria MZS. 344921 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1094 records from crsn_data. 57269 records from JPB - Herbário Lauro Pires Xavier. 3465 records from Bryoquel : Spécimens de bryophytes de l'herbier de la Société Québécoise de Bryologie. 5 records from University of British Columbia Herbarium (UBC) - Fungi Collection. 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 304 records from Ájtte. 10 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 56665 records from EAC - Herbário Prisco Bezerra. 20 records from (Figure 4) Dinoflagellate measurements from sediment core DA06-139G during RV Dana cruise in 2006. 309037 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 28175 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 39954 records from Cartographie des Leguminosae (Fabaceae) en France. 244169 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 5632 records from USGS South Florida Fish and Invertebrate Assessment Network Harvest. 619 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN.. 14369 records from Herbario de la Universidad Industrial de Santander. 34003 records from Bryophyte herbarium, Göttingen (GOET). 3947 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 10 records from Carabidae of the Carpathians. 40498 records from R - Herbário do Museu Nacional. 892304 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 33314 records from Marine Conservation Society - Seasearch Marine Surveys. 1714 records from The Flora of County Clare. 2786 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 50 records from EcoRecord - Odonata (Dragonfly and Damselfly) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 4 records from Seodaemun Museum of Natural History Fossil. 5 records from Chenopodium vulvaria. 492 records from Verneplan Hjerkinn karplanter. 433 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 556 records from Countryside Council for Wales - Freshwater Site Visits. 3165 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Santuario de Flora y Fauna Los Colorados. 1115 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 11648 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 2408 records from Ecology, structure and dynamics of private plantations of Teck (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 2097 records from Kartlegging av dragehode. 1 records from Lichen specimen database of Faurie collection. 266 records from Registros de flora de las caracterizaciones rápidas de coberturas en los municipios de Beltrán y Guataquí, Cundinamarca. 172535 records from Tromsø Museum, Vascular plants. 1 records from Queen Victoria Museum Art Gallery provider for OZCAM. 4645 records from Inventaire National du Patrimoine Naturel : Flore de Sologne. 4 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1170D sediments. 18047 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 105 records from Specimens from India at the Natural History Museum at the University of Oslo (NHM-UiO). 1 records from Arachnida e Myriapoda Museu Nacional (MNRJ ARAC). 102730 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 224614 records from Vascular Plant Herbarium, Trondheim (TRH). 365952 records from Données ONF Faune-Flore-FOnge. 99096 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 19 records from Scottish Wildlife Trust - Small Cow-wheat distributions for Scotland 1999 to 2005. 12 records from Balanophora coralliformis (Balanophoraceae), a new species from Mt. Mingan, Luzon, Philippines. 18523 records from New Zealand Biodiversity Recording Network. 1210996 records from Vascular Plants, Field notes, Oslo (O). 4 records from Observaciones de Especies Silvestres (by Charif Tala). 1426743 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 610 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 1709158 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 24083 records from Herbarium Amazonense. 54 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 1082339 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 3323 records from Plant (NSMK-PL). 2252 records from Nijmegen Natural History Museum (NL) – Herbarium. 769 records from Digital Florula - Palo Verde Biological Station. 1471 records from EcoRecord - Bryophyte records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 8913 records from Wilson Botanical Garden - Las Cruces Biological Station. 3892 records from SLUI - Herbário Rosa Mochel. 2387 records from The French Collection of Medicago truncatula. 2546 records from Nature Locator - PlantTracker data from 2012 onwards. 1 records from SMNS Palaeontological collection - Tertiary mammals. 27461 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 493 records from Phanérogames recensés aux Monts Nimba. 9828 records from Ecofact. 1 records from Die Milbenfauna der Nordseeinsel Wangerooge. 179796 records from UB - Herbário da Universidade de Brasília. 23300 records from Central African Plants. 16 records from MfN - Fossil Fish Collection. 51 records from Université Pédagogique Nationale de Kinshasa (UPN) - Données botaniques (2011)- Projet CABIN. 2 records from The Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 85248 records from Green Plant Herbarium (TRT). 58 records from Naturalis Biodiversity Center (NL) - Mollusca. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 27324 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 221813 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 145027 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 6 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 25528 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 72 records from Amaranthaceae Observations Tanzania and Kenia. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 4 records from Collection Diptera - SMF. 15 records from Geologisch-Paläontologische Sammlung Universität Leipzig. 72007 records from Instituto de ciencias naturales. 1 records from Australian Museum provider for OZCAM. 3137 records from Herbarium - Las Cruces Biological Station. 177494 records from Segundo censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 19821 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 7679 records from Herbier CNRST/INERA. 2707 records from Miscellaneous Vascular Plants. 5528 records from Biodiversity Now / Nature Check (Biodiversitet Nu / NaturTjek). 399 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 30 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 1453 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 2 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 5067 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 67090 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 8892 records from Liverworts (Marchantiopsida) and Hornworts (Anthocerophyta) of Denmark. 2 records from Naturalis National Natural History Museum (NL) – Cnidaria and Porifera fossils. 50 records from Fossil (NSMK-FO). 41 records from Registros de hongos en áreas protegidas de la Argentina. 1250 records from Plant Observation Records of Japan. 2354 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 13 records from SMNS Palaeontological collection - Invertebrates (Palaeozoic, Mesozoic). 646368 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 5570 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 2420 records from SANT-Bryo. 236882 records from Allan Herbarium (CHR). 9423 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 83116 records from Botanical Society of the British Isles - Changing Flora of Glasgow 1982-2000. 2596 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 207105 records from SysTax - Botanical Gardens. 1179 records from Herbarium of University of Białystok - Vascular Plants. 2272 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Tanacetum vulgare dominated forb vegetation. 527 records from National Trust - Heigham Holmes species data held by The National Trust. 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 407685 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 5544 records from Herbarium specimens of CBNA (GAP). 156257 records from Flore de Franche-Comté. 238 records from Korean Peninsula Flora. 6482 records from BioFresh Pond Data. 193 records from Herbarium BSG Hepaticopsida. 34 records from The nematodes collection (IN) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3341 records from SORO - Herbário do Centro de Ciências e Tecnologias para a Sustentabilidade. 13661 records from HPL - Herbário do Jardim Botânico Plantarum. 50682 records from CZE National PGR Inventory. 633 records from Thames Valley Environmental Records Centre - English Nature Oxfordshire Fen Survey 1990-1991 (A Comparative Survey of Rich Calcareous Fens of Oxfordshire) (as held by Thames Valley Environmental Records Centre). 9420 records from Sussex Biodiversity Record Centre - Sussex Bryophyte Atlas Data edited by Howard Matcham. 522 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 91 records from Botanical Society of the British Isles - RISC Botanical Non-Native Species Records. 2481 records from Neptune Deep-Sea Microfossil Occurrence Database. 498 records from Inventory Pobè forest in South East of Benin. 13464 records from Scottish Natural Heritage - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by Scottish Natural Heritage. 499 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 3 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Diptera Records up to Dec 2011. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 29279 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 89236 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 941 records from Checklist of Serengeti Ecosystem Grasses. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2203 records from Colección Nacional de Actuopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 5442 records from Orchid Herbarium Collection. 2 records from Guadeloupe_Insectes. 99 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 689712 records from Vascular Plant Herbarium, Oslo (O). 7120 records from The Bergius Herbarium. 1 records from Mycology herbarium, Oslo (O). 35952 records from Occurrences in SinBIOTA. 779 records from Guadeloupe_Ananas. 18460 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4300 records from University of Amsterdam (NL) - Páramo Vegetation Research, Sumapaz-Bocagrande-Chisaca paramo complex, Colombia. 1248 records from LAGPLON - Nouvelle-Calédonie. 9377 records from tan-database. 51785 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 1394 records from Anymals+plants - Citizen Science Data. 15057 records from Natural History Museum Rotterdam (NL) - Plantae collection. 3786 records from Vascular plants of Amrum 2007-2008. 678682 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 2020 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 7607 records from Naturhistorisches Museum Mainz, Herbarium von Ruprecht Düll. 4160 records from Herbario de Briófitos de la Universidad de Salamanca: SALA-Bryo. 53350 records from E. C. Smith Herbarium (ACAD). 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 1101 records from Colección de referencia del Herbario CUVC de la Universidad del Valle. 9258 records from Big Island Invasive Species Committee - Pest Reports - 2005-2010. 43018 records from BUT Friesner Herbarium. 897 records from Quantitative Phytoplankton data from Irish lakes (EPA). 120 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 1761 records from Aggregate Industries - Grassland and Heathland Survey at Bardon Hill 2008/9. 180673 records from The Flora of County Waterford. 794 records from Inventaire National du Patrimoine Naturel : CBN Alpin de Gap. 3289 records from HDJF - Herbário Dendrológico Jeanine Felfili. 1436 records from Fundación Miguel Lillo - Colección Fanerogámica. 1494 records from Countryside Council for Wales - Stoneworts in Wales. 1134 records from SWECO. 2728 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 1701 records from Census of plant species in Monts-Kouffè regions, center Benin. 5089 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 19698 records from Moss herbarium, UiB. 41732 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 995 records from Herbario HUAZ Enrique Forero. 15848 records from Herbarium Erlangense. 4 records from Invertebrata Collection of Institute of Systematics and Evolution of Animals. 337 records from Caracterización de coberturas vegetales en el páramo de Santurbán. 25632 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 302 records from Macroinvertebrate abundance in river biotopes across England and Wales. 839 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 442 records from Herbier Boreal Confluence (BOUM). 42994 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 124 records from New Zealand Fungal and Plant Disease Collection (PDD). 1696 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 1 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2010. 63 records from SuLaMa yam occurence data. 1537 records from Collections of Phytoplankton at BGBM. 4 records from Odonata Collection. 62 records from LAGPLON - Polynésie francaise. 18 records from Thirteen new records of ferns from Brazil. 7032 records from EAN - Herbário Jaime Coelho de Moraes. 346 records from Levantamento do estrato arbustivo da vegetação de campina do RDS Uatumã. 18152 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 9439 records from BioGIS - Vascular plants - SPNI. 1 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2006. 67 records from Chenopodium & Dysphania. 245222 records from Vascular Plants, Field notes, Trondheim (TRH). 3939 records from Census of plant species in Pahou forest reserve. 3664 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 2 records from Fish collection, Natural History Museum, University of Oslo. 3543 records from Vascular plants in Danish coastal meadows. 448 records from Biodiverisity Group, Dept. of Environment, Food and Agriculture,Isle of Man Government - Japanese Knotweed Records in the Isle of Man 1991-2008. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 42979 records from The census of national forest of Benin .. 2418782 records from British Bryological Society - Bryophyte data for Great Britain from the British Bryological Society held by BRC. 10179 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 165 records from Diversidad florística y estado de conservación en dos ventanas de paisaje de la UPR Tunjuelo priorizadas: Usme y Ciudad Bolivar, Bogotá. 65 records from Alien Species in Poland - Plants. 30 records from Tab. 6: Relative Abundanz einzelner Arten der Endofauna. 256 records from Colección del Herbario del Jardín Botánico de la Universidad Nacional de Colombia Sede Caribe. 6 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 6 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 5 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 32482 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 26346 records from Marie-Victorin Herbarium (MT) - Bryophytes. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 4664 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Bryophytes. 9731 records from Fundación Miguel Lillo - Colección Criptogámica. 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 1091 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Trawl. 51906 records from SysTax - Herbaria. 57 records from (Supplementary data 1) Count data of the observed dinoflagellate cyst species from sediment core GeoB10709-5. 74794 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 1 records from Insect (HUNM-IN). 992 records from Plant (NHMK-PL). 8324 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 186 records from Carabidae of Poland. 376 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 485 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 179405 records from Geneva Herbarium – General Collection (G). 1 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 288 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramo "El Almorzadero", Colombia. 2223 records from BoGART. 317480 records from Instituto de Botánica Darwinion. 1775 records from Algae, Specimens, Agder naturmuseum (KMN). 69 records from aquap. 49 records from Collection Paleontology - GPIT. 1014 records from JOIw - Xiloteca Joinvillea. 1343 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 69 records from (Figure 1) Stratigraphic distribution of taxa at DSDP Hole 79-547B. 8329 records from Nijmegen Natural History Museum (NL) - Herbarium. 250190 records from Northern Ireland Environment Agency - EHS Species Datasets. 17979 records from SJRP - Herbário de São José do Rio Preto. 59980 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 1 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2000. 4232 records from Herbarium WRSL, Main Collection. 50584 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 59 records from Calcareous Algae. Report on the Danish Oceanographical Expeditions 1908-10 to the Mediterranean and adjacent seas. 721804 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 1639 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 432 records from Guadeloupe_Ignames. 2000 records from Herbario Virtual Bosques Secos de Colombia - Sección Herbario Universidad de Córdoba (HUC). 67 records from AMNH Invertebrate Paleontology Collection. 7970 records from UFMT - Herbário UFMT. 44351 records from Flora of the Stołowe Mts.. 485166 records from CAS Botany (BOT). 6 records from CUMV Bird Collection (Arctos). 4 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 184530 records from Atlas des plantes vasculaires de Lorraine. 20305 records from CPAP - Herbário CPAP. 1 records from South Australian Museum Australia provider for OZCAM. 458 records from Barley French National Collection. 1 records from Foraminíferos. 540150 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain). 17 records from UCDavis - Western USA - Monarch Butterflies - 1892-2005. 5 records from Lichen herbarium, UiB. 3880 records from Algae herbarium, Trondheim. 18414 records from National Museum of Natural Science. 504 records from Dieta y preferencias alimenticias de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 5452 records from Systematic census of the private plantations of the firewood of the Benin .. 11 records from Nottinghamshire Biological and Geological Records Centre - UK abstract from Nottingham City Museums & Galleries (NCMG) Insect Collection Baseline database. 2909 records from Herbarium specimens of Limog
Keywords: GBIF; biodiversity; species occurrences